Discovery of a DNA methylation episignature for Weiss-Kruszka syndrome - Haley McConkey; Liselot van der Laan; Sourav Ghosh; Lotte Kleinendorst; Michael A. Levy; Jessica Rzasa; Johanna M. van Hagen; Quinten Waisfisz; Heidi L. Schulz; Corina Heller; Kerstin Huhn; Carolin D. Obermaier; et al. (Human Genetics, 2026)
Weiss-Kruszka syndrome (WSKA; OMIM 618619) is a rare autosomal dominant neurodevelopmental disorder caused by haploinsufficiency of ZNF462, a zinc-finger transcription factor involved in chromatin regulation and early embryonic development. WSKA is characterized by developmental delay, hypotonia, craniofacial dysmorphic features (around 8) and variable congenital anomalies. Genome-wide DNAm profiling was performed on peripheral blood DNA from 9 WSKA cases with (likely) pathogenic ZNF462 variants and matched controls to look for differential methylation. Analysis using the EpiSign™ pipeline identified a robust DNAm pattern, or episignature, specific to WSKA syndrome. Supervised machine-learning classification demonstrated high sensitivity and specificity, with reproducibility confirmed by leave-one-out cross-validation, as well as correctly classifying a validation case with a pathogenic ZNF462 variant. Comparative analysis revealed partial overlap of genome-wide DNA methylation changes between the WSKA episignature and other neurodevelopmental disorders involving chromatin regulators. Functional annotation of differentially methylated probes and regions demonstrated enrichment for pathways related to neurodevelopment, neuron function and cell adhesion. These findings define and validate a distinct DNAm episignature for WSKA, providing a valuable diagnostic biomarker to support variant classification and offering insight into the epigenomic consequences of ZNF462 haploinsufficiency.

Wetlands function as a nature-based microcystin remediation system - Jessica Lerminiaux; Matthew J. Bogard; Jonathan K. Challis; Mia Lahiji; Peter R. Leavitt; Kerri Finlay (Harmful Algae, 2026)

Observations of Shelling Behavior and Potential Evidence of Vertical Social Learning by Bottlenose Dolphins in the Great Sandy Marine Park, Queensland Australia - Alexis L. Levengood; Georgina V. Hume; Jessica M. Buckman; Isla Steel; Bridget E. Toohey; Peter Lynch; Cassandra Smith (Marine Mammal Science, 2026)

Corrigendum to “Fate and transport of viruses, bacteria and antimicrobial resistance associated with wet wipes and microplastics through wastewater treatment to coastal waters” [Water Research (2026) /126281] - Jessica L. Kevill; Margaret E. Knight; Yashi Jain; Karina A. Marsden; Rachel C. Williams; Kate Herridge; Winnie Courtene-Jones; Peter Robins; Shelagh K. Malham; Davey L. Jones (Water Research, 2026)

Fate and transport of viruses, bacteria and antimicrobial resistance associated with wet wipes and microplastics through wastewater treatment to coastal waters - Jessica L. Kevill; Margaret E. Knight; Yashi Jain; Karina A. Marsden; Rachel C. Williams; Kate Herridge; Winnie Courtene-Jones; Peter Robins; Shelagh K. Malham; Davey L. Jones (Water Research, 2026)

Pheromone-based mating disruption suppresses cigarette beetle (Lasioderma serricorne) trap captures in a large tobacco processing facility - Peter A. Edde; Jessica Lindenmayer; Tim Reid; Thomas W. Phillips (Journal of Stored Products Research, 2026)

Evaluating Hg speciation in an offshore gas export pipeline and the utility of pXRF for screening Hg contamination - Lhiam Paton; Bernt Johannessen; Peter Kappen; Pauline Treble; Jessica Hamilton; Tom Cresswell (Journal of Hazardous Materials, 2026)

Sodium chloride hydrates provide an archive of ocean fluid freezing rates at icy worlds - Rachael E. Hamp; Mark G. Fox-Powell; Peter Fawdon; Christoph G. Salzmann; Jessica P. Hogan; Milz L. Beaumont; Liam Perera; Stephen P. Thompson (Earth and Planetary Science Letters, 2026)

Characterising subsea gas pipeline contaminants to inform decommissioning practices, an ecosystem perspective - Tom Cresswell; Henri Wong; Matthew Johansen; Peter Kappen; Jessica Hamilton; Francesca Gissi; Sue Brown; Lhiam Paton; Simon Apte (Journal of Hazardous Materials, 2026)

Over‐Representation of Sperm‐Associated Deleterious Mutations Across Wild and Ex Situ Cheetah ( Acinonyx jubatus ) Populations - Jessica A. Peers; Heather R. Sibley; Ellie E. Armstrong; Adrienne E. Crosier; Will J. Nash; Klaus‐Peter Koepfli; Wilfried Haerty (Molecular Ecology, 2026)
As purifying selection becomes less effective and inbreeding increases, small populations frequently develop an increased load of genome‐wide deleterious mutations. Reflecting this pattern, deleterious mutations in genes associated with fertility and immunity have previously been identified in the cheetah ( Acinonyx jubatus ), which has had a low effective population size for at least the last 10,000 years. However, the distribution of deleterious mutations across cheetah populations is currently unknown. Here, we analysed novel whole genome resequencing data from 30 ex situ and 9 wild cheetahs. We investigated variation in genetic diversity, genomic measures of inbreeding, and the distribution of deleterious mutations across cheetah populations. South Sudanese and Tanzanian cheetahs showed higher inbreeding and realised load, while Namibian cheetahs had a higher proportion of population‐specific deleterious mutations. Genes containing high‐ or moderate‐impact deleterious mutations were significantly enriched for sperm‐related functions, highlighting putative causative loci associated with poor sperm quality in cheetahs. Similar levels of genetic diversity and inbreeding were observed in ex situ cheetahs compared to their wild counterparts, providing empirical evidence of the efficacy of captive breeding programmes in maintaining genetic variation in ex situ populations.

Description and Effectiveness of Environmental Approaches to Cognitive Rehabilitation for Traumatic Brain Injury: A Systematic Review of Randomised Controlled Trials - Ella Waldman; Jennie Ponsford; Michal Boneh; Jessica Trevena-Peters (Neuropsychology Review, 2026)
Interventions addressing cognitive impairments after traumatic brain injury (TBI) often rely on survivors’ relatively preserved capacity to learn, initiate, and consistently use rehabilitation strategies, along with the ability to apply strategies in various contexts. The cognitive functions required for such active engagement in rehabilitation are commonly impaired after TBI, consequently limiting the benefits of many existing cognitive rehabilitation approaches. Environmental approaches, which involve manipulating the environment to support cognition and function, may benefit TBI survivors, as they do not require active involvement of the user to initiate and maintain their use. Although these approaches are recommended by experts and frequently used, their effectiveness and components are largely unknown. We conducted a systematic review, searching for randomised controlled trials of adults with TBI who received environmental interventions for cognitive or related functional outcomes, compared to any control. Two reviewers independently undertook screening and data extraction following a standardised protocol. Risk of bias was assessed using Joanna Briggs Institute Critical Appraisal Instruments. Five studies were included in the review. Environmental intervention approaches included prompting (three studies) and trained communication partners (two studies), both of which demonstrated relatively strong evidence for their effectiveness. Key methodological limitations included insufficient blinding to group allocation, randomisation concealment, reliability of outcome measurement, and lack of baseline similarity between groups. Whilst environmental approaches involving prompting and trained communication partners demonstrate potential for improving the daily functioning of individuals with TBI, further research is needed. Systematic review registration number: PROSPERO CRD42024592708, registered September 2024.

A Model for Clinician and Staff Education in the Engagement of American Indians in Genomic Research - Ursa Brown-Glaberman; Alissa Greenbaum; Koby Blackwater; Raven Chavez; Cindy K. Blair; Jude Khatib; Jacklyn Nemunaitis; V. Shane Pankratz; Bethany Davis; Jill Peters; Kelsey Pettes; Mallery Quetawki; et al. (Journal of Cancer Education, 2026)
Despite notable differences in cancer incidence and outcomes, fewer American Indians have participated in cancer research and genomic testing relative to their population size. Contributing factors include historical scientific mistrust, lack of culturally appropriate research methodologies, and limited access. With the launch of a cancer genomic sequencing trial in American Indians from the Southwestern United States (US), clinicians and staff encountered challenges engaging patients, recognizing the complexity of research in this population. We describe a novel approach to educate study team members regarding genomic cancer testing and research in American Indian populations. Clinical faculty and staff investigators participated in (1) hands-on experiential workshops related to core beliefs and healthcare in American Indians and (2) the development of provider-facing educational materials. After participation in the workshops, investigators, including American Indian researchers, created two sets of provider-facing materials and implemented them in clinic. The first provided a summary detailing trial eligibility, procedures, and privacy safeguards. The second outlined topics fostering respectful engagement of American Indians in research, outlining core beliefs including the importance of family and community in decisions, a framework of inherent cycles in human life and nature, the importance of visual aids, and the complementary nature of traditional healing. An approach incorporating cultural training for clinicians and staff is feasible when engaging American Indians of the Southwestern US in genomic research. This methodology may serve as a model for future initiatives to engage with American Indians in cancer research and in both clinical and research related genomic testing.

Linking soil nematode community structure with pomegranate root phytochemicals in Limpopo Province, South Africa - Ebrahim Shokoohi; Talita Jessica Mnisi; Peter Masoko (Biologia, 2026)
This study examined the diversity, functional structure, and ecological relationships of nematode communities associated with the rhizosphere of pomegranate ( Punica granatum L.) in Limpopo Province, South Africa, with particular focus on their interaction with soil physicochemical properties and root phytochemicals. A total of 20 nematode genera were identified, representing five feeding guilds: herbivorous, bacterivorous, fungivorous, predators, and omnivorous. The nematode assemblage showed that herbivorous taxa (P-p class 3) were represented by Rotylenchulus , Helicotylenchus , Pratylenchus , Tylenchorhynchus , and Rotylenchus , while bacterivorous nematodes ( Acrobeloides , Pseudacrobeles, Prismatolaimus, Geomonhystera ) accounted for the largest proportion of free-living nematodes. Food web analysis showed a gradient from disturbed, nitrogen-enriched systems (high enrichment index, low structure index) to mature, structured webs, indicating variation in soil fertility and biological regulation across the orchard. Principal component analysis (PCA) explained 100% of total variation (PC1 = 55.08%, PC2 = 44.92%), revealing that nematode distribution was primarily driven by soil pH, electrical conductivity (EC), and nitrogen content. Pratylenchus and Rotylenchulus were negatively correlated with EC ( r = -0.99). In addition, Pratylenchus and Rotylenchulus showed strong positive correlations with ammonia ( r = 0.99) and nitrate ( r = 0.98). Phytochemical analysis revealed that total phenolic, flavonoid, flavonol, and tannin contents were negatively correlated with Tylenchorhynchus ( r = -0.866) and Xiphinema ( r = -0.866), suggesting suppression of these nematodes by polyphenolic compounds and Trichodorus ( r = 0.866), suggesting an increase in this nematode by polyphenolic compounds. In conclusion, the findings highlight the regulatory role of root phytochemicals and soil properties in shaping nematode community composition, indicating that phenolic-rich pomegranate roots may contribute to natural suppression of herbivorous nematodes and enhance soil ecological stability.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Prevalence of Enterocytozoon bieneusi and Encephalitozoon spp. in Swedish patients with suspected gastrointestinal parasite infection: a cross-sectional molecular study - Jessica Ögren; Anna J Henningsson; Silvia Botero-Kleiven; Andreas Matussek; Peter Wilhelmsson (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Network-Scale Patterns and Drivers of Microcystins in a Heavily Impacted Watershed - Jessica Lerminiaux; Kerri Finlay; Peter R. Leavitt; Samuel G. Woodman; Matthew J. Bogard (Ecosystems, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Developing and testing of a winegrape phenology model for Australian conditions - Dane S. Thomas; Wendy Cameron; Peter T. Hayman; Marcos Bonada; Victor O. Sadras; Joanna M. Gambetta; Jessica Y.C. Jolley; Paul R. Petrie (Agricultural and Forest Meteorology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A 2026 horizon scan for biodiversity conservation in South Africa - Colleen L. Seymour; Krystal A. Tolley; Tsungai Zengeya; Dian Spear; Jeran A. Cloete; Anisha Dayaram; Jessica M. da Silva; Graham J. Alexander; Kate Handley; Grant S. Joseph; Lavhelesani D. Simba; Kate Snaddon; et al. (Ambio, 2026)
Horizon scans identify potential changes, enabling proactive rather than reactive conservation strategies. Here, in a follow up to the 2020 horizon scan, 14 biodiversity professionals from different sectors identify ten emerging issues potentially relevant to biodiversity conservation in South Africa over the next 5–10 years. The issues identified highlight three critical needs: adaptive governance systems, cross-sectoral collaboration capacity, and vigilance around new technologies that may simultaneously offer solutions and create new environmental pressures. We plotted these issues along axes of social agreement and scientific certainty, to ascertain whether issues might be "simple" (amenable to solutions from science alone), "complicated" (socially agreed upon but technically complicated), "complex" (scientifically challenging and condisderable levels of social disagreement) or "chaotic" (high social disagreement and highly scientifically challenging). Only one issue was likely to be addressed with improved science alone, but the remainder were all “complex”, requiring social, economic and political engagement.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Predicting norovirus contamination and antimicrobial resistance in coastal waters from community and hospital-derived sources - Thomas W. Clough; Reshma Silvester; Jessica Kevill; Kata Farkas; Shelagh K. Malham; Gareth Cross; Peter Robins; Davey L. Jones (Water Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Bryde's whale ( Balaenoptera edeni ) occurrence and foraging behaviour along the east coast of Australia - Vanessa Pirotta; Daniele Cagnazzi; Brett Dixon; Simon Millar; Jessica Millar; Greg Pickering; Paul A. Butcher; Karen A. Stockin; Katharina J. Peters (New Zealand Journal of Marine and Freshwater Research, 2025)
Despite their global occurrence in warm‐temperate waters and their suspected non‐migratory lifestyle, Bryde's whales ( Balaenoptera edeni spp.) are considered the least‐known large baleen whale species. In Australian waters, information on their distribution, ecology and behaviour is scarce. This study documents Bryde's whale occurrence and foraging behaviours along the Australian East Coast using opportunistic citizen science sightings via drone aerial photography, vessel and land‐based observations. We observed foraging in both shallow (seafloor visible, beach and breaking waves present) and deep waters. We observed a range of foraging behaviours including lunge feeding (exhibited by individual whales and in pairs), sub‐surface and surface skim feeding (shallow waters only) and described multispecies associations. We describe a potentially novel feeding behaviour in shallow waters, where Bryde's whales are feeding directly within or behind the surf break ( shallow water surf feeding ). We quantify the presence of mother‐calf pairs in Australian waters, highlighting the use of these waters for potential calving. This study provides insights into Bryde's whale occurrence and foraging behaviour in both shallow and deep waters of eastern Australia.

Assessing recovery and conservation of Australian freshwater fishes with the IUCN Green Status of Species and structured expert elicitation - Maiko L. Lutz; David G. Chapple; Molly K. Grace; Luciano B. Beheregaray; Chris J. Brauer; Iain Ellis; Adam Kerezsy; John D. Koehn; Mark Lintermans; Jarod P. Lyon; Matthew McLellan; Luke Pearce; et al. (Conservation Biology, 2025)
The International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), introduced in 2021, is a global standard of measurement used to assess the level to which a species has recovered (i.e., is viable and providing its ecological function across its entire range). It is also used to evaluate how a species has responded to past conservation actions and the expected conservation gains and recovery potential it would receive in the short‐ and long‐term future. Preliminary application of the GSS method has relied on expert knowledge from individuals or small groups of specialists. However, more accurate and reliable results are likely to be produced by formally eliciting individual judgments from a diverse range of experts, followed by discussion, reevaluation, and synthesis of these judgments. We developed a method in which 2 structured expert elicitation workshops are used to conduct GSS assessments and applied this method to 8 Australian freshwater fish species from the Murray–Darling Basin. We integrated the investigate, discuss, evaluate, aggregate protocol into the GSS methods; experts assessed the species’ IUCN Green Score (percent recovery) in the current state and for 5 other scenarios in the past and future with and without conservation. Four GSS conservation impact metrics were calculated based on the averages of expert judgments. Experts forecasted that impact in the short‐term would be minimal (i.e., conservation gain metric = zero or low) for 5 of the 8 species because targeted and maintained conservation actions are often lacking. In contrast, experts indicated long‐term recovery potential would be considerably higher if implementation of appropriate recovery activities could be sustained (all 8 species had medium or high recovery potential). We concluded that the GSS is well suited to a modified workshop approach because it aims to reduce biases associated with expert judgments and encourages valuable knowledge sharing among experts.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Knock Out of miRNA-30a-5p and Reconstitution of the Actin Network Dynamics Partly Restores the Impaired Terminal Erythroid Differentiation during Blood Pharming - Jessica Thiel; Duran Sürün; Desiree C. Brändle; Madeleine Teichert; Stephan R. Künzel; Ulrike Friedrich; Andreas Dahl; Kristin Schubert; Ignacy Rzagalinski; Andrej Shevchenko; Sofia Traikov; Peter Mirtschink; et al. (Stem Cell Reviews and Reports, 2025)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

Origins and fluxes of gas emissions from the Central Volcanic Zone of the Andes - J. Maarten de Moor; Peter H. Barry; Alejandro Rodríguez; Felipe Aguilera; Mauricio Aguilera; Cristóbal Gonzalez; Susana Layana; Agostina Chiodi; Fredy Apaza; Pablo Masias; Christoph Kern; Jaime D. Barnes; et al. (Journal of Volcanology and Geothermal Research, 2025)

Public support for food subsidy and tax scenarios to promote healthy and sustainable diets: Evidence from deliberative forums in two UK locations - Hannah Forde; Peter Scarborough; Lucy Yates; Jessica Renzella; Mark Sheehan; John Buckell; Alice O’Hagan; Sian Taylor; Jane Ward; Annie Connolly; Mike Rayner; Richard Smith; et al. (Food Policy, 2025)

Long-term exposure to extreme heat and cold and cognitive decline in older adults: Results from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort - Peter S. Larson; Phillipa Clarke; Robert Melendez; Jessica M. Finlay; Ketlyne Sol; Suzanne Judd; Iris Gomez-Lopez; Anam Khan; Carina J. Gronlund (Environmental Research, 2025)

Fossilisation of Fish Soft Tissue in Oxidative Microniches of Anoxic Sediments - Amy L. Elson; Lorenz Schwark; Paul F. Greenwood; Madison Tripp; Alex I. Holman; Michael E. Böttcher; Peter Hopper; Robert H. C. Madden; Luke M. Brosnan; Jessica H. Whiteside; Stephen F. Poropat; Lance Grande; et al. (Environmental Microbiology, 2025)
Organic analyses of past organisms enhance our understanding of Earth's evolutionary history, complementing the macrofossil record. Biomolecular remains are typically vulnerable to diagenetic mineralisation, but can persist in exceptional depositional settings such as Lagerstätten. Their preservation is usually linked to anoxic conditions that exclude aerobic degraders. However, we report intact skin tissue of the fossil fish Diplomystus dentatus from the Fossil Basin Lagerstätte (USA), preserved through phosphate permineralisation in an oxygen‐enriched microenvironment. Notably, only the skin with scales retained tissue integrity, and this organic material was closely associated with fluorapatite absent from the surrounding matrix. Geochemical analyses revealed higher oxidation states in the skin than in vertebrae and bones, likely due to early degradation of the fatty acid‐rich dermis. Redox‐sensitive biomarkers and isotopic data (δ 15 N) indicated a less reducing environment in the skin region compared to bones and the eye, yet more reducing than the surrounding sediment. This localised oxygen enrichment fostered sulphide‐oxidising bacteria, evidenced by mineral sulphates (barite) found only in the skin. Phosphatisation was likely driven by dermal breakdown and the release of H+, reducing alkalinity and enabling phosphate mineralisation over the carbonate system.

Links between poverty, climate-induced migration and deforestation in western Madagascar - Herizo T. Andrianandrasana; Nikoleta Jones; Fabiola F. Viraina; Chrysovalantis Malesios; Marco Campera; Sama Zefania; Peter R. Long; Stéphanie Panichelli-Batalla; Nigel M. Richardson; Jessica Savage (Environmental Development, 2025)

End-of-life pathology in UM-HET3 mice treated with 16 α‑hydroxyestradiol or late‑start canagliflozin - Jessica M. Snyder; David E. Harrison; Ron Korstanje; Brett Ginsburg; Peter C. Reifsnyder; James Nelson; Scott Leiser; Catherine Kaczorowski; Denise M. Imai; Adam B. Salmon; Randy Strong; Warren Ladiges; et al. (GeroScience, 2025)
Canagliflozin (Cana) started at 16 months of age and 16-hydroxy-estradiol (OH_Est) started at 12 months each led to significant increases in lifespan in male UM-HET3 mice but significant decreases in female lifespan. To seek insights into the basis for these sex-specific effects, we performed end-of-life histopathological analyses of control and treated mice for all three interventions testing program sites. There were no significant drug-induced alterations in inferred cause of death, although statistical power was low for such comparisons. Tabulation of incidental lesions (i.e., combining lethal and non-lethal lesions) revealed a complex set of significant and near-significant changes caused by each of the two agents, in some cases absent, or even opposite in direction, in one of the two sexes. The analysis did not, however, reveal a clear pattern that would explain the selective sex-specific effects of either agent on lifespan. It is plausible that the female-specific harm induced by each of these agents could reflect harmful or toxic effects that are not easily detectable by histopathological examination.

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Impact of sarcopenia and obesity on skeletal muscle size, gene expression, and mitochondrial function - Hector G. Paez; Christopher R. Pitzer; Jessica L. Halle; Peter J. Ferrandi; James A. Carson; Junaith S. Mohamed; Stephen E. Alway (GeroScience, 2025)
Skeletal muscle is a primary tissue of dysfunction during both aging and obesity. Recently, the coincidence of obesity and aging has gained attention due to the intersection of the obesity epidemic with an aging demographic. Both aging and obesity are associated with marked defects in skeletal muscle metabolic health. Despite these findings, we have a poor understanding of how obesity and aging may interact to impact skeletal muscle mass and metabolic health. Therefore, we investigated the impact of high-fat diet (HFD)-induced obesity on skeletal muscle mass, mitochondrial function, transcriptomics, and whole-body metabolism in young and aged mice. We observed main effects of diet and age on several measures of whole-body metabolic function (VO 2 , VCO 2 , and RER). Complex I-driven mitochondrial proton leak was significantly elevated by HFD-induced obesity across both age groups; however, a main effect of aging for reduced complex I leak was detected in the soleus muscle. Interestingly, aged animals fed a HFD did not exhibit lower muscle mass than chow-fed young animals, but did present with stark increases in muscle triglyceride content and a unique transcriptional response to HFD. HFD-induced obesity impacted the muscle transcriptome differently in the muscles of young and aged mice, indicating that obesity can change altered gene expression with age. Our findings suggest that the presence of obesity can both compound and counteract age-associated changes to muscle mass, gene expression, and mitochondrial function.

Comparative impact of sunlight and salinity on human pathogenic virus survival in river, estuarine, and marine water microcosms - Jessica L. Kevill; Kate Herridge; Xiaorong Li; Kata Farkas; Shelagh K. Malham; Peter Robins; Davey L. Jones (Water Research, 2025)

Multi-omics Quality Assessment in Personalized Medicine Through European Infrastructure for Translational Medicine (EATRIS): An Overview - Patricia Alonso-Andrés; Davide Baldazzi; Qiaochu Chen; Elisa Conde Moreno; Lorena Crespo-Toro; Kati Donner; Petr Džubák; Sara Ekberg; Maria Laura García Bermejo; Daniela Gasparotto; Bishwa Ghimire; Jolein Gloerich; et al. (Phenomics, 2025)
Molecular characterization of a biological sample, e.g., with omics approaches, is fundamental for the development and implementation of personalized and precision medicine approaches. In this context, quality assessment is one of the most critical aspects. Accurate performance and interpretation of omics techniques is based on consensus, harmonization, and standardization of protocols, procedures, data analysis and reference values and materials. EATRIS, the European Infrastructure for Translational Medicine ( www.EATRIS.eu ), brings together resources and services to support researchers in developing their biomedical discoveries into novel translational tools and interventions for better health outcomes. Here we describe the efforts within the Horizon 2020 EATRIS-Plus project and activities of member facilities of EATRIS towards quality assessment of pre-clinical sample processing, clinical omics data generation, multi-omics data integration, and dissemination of the resources in a Multi-Omics Toolbox, which is the principal deliverable of the EATRIS-Plus project for the consolidation of EATRIS towards translational medicine.

Impacts of Primary Non-Inversion Shallow Tillage and Moldboard Plowing on the Potato Early Dying Disease Complex in Prince Edward Island, Canada - Dahu Chen; Judith Nyiraneza; Kamrun Nahar; Danielle Murnaghan; Jessica Matheson; Ryan Barrett; Kyra Stiles; Tandra D. Fraser; Rick D. Peters (American Journal of Potato Research, 2025)
Conservation tillage has shown potential to improve soil health and enhance crop productivity in various cropping systems. Moldboard plowing (MP) in the fall prior to the potato phase is a conventional practice in Prince Edward Island (PEI), Canada, which leaves the soil prone to erosion and soil organic matter decline. Potato early dying disease complex (PED) is a major yield limiting factor in potato production in PEI. The objective of this four-year (2019–2022) study conducted in 14 commercial fields was to determine the effect of non-inversion shallow tillage (ST) in comparison with MP on PED pathogen population density in the spring at potato planting time and in the fall post-potato harvesting, and on PED disease severity. Root lesion nematodes ( Pratylenchus spp ., RLN) were detected in all fields. Verticillium dahliae was the predominant species in all fields, while V. albo-atrum was sporadically detected in a few samples. The population density of the RLN and V. dahliae varied among the fields. In the spring samples, V. dahliae density was significantly higher in 5 of the 14 fields with the ST treatment compared with MP. RLN density was significantly higher in one of the 14 fields with the ST. When averaged across all fields, V. dahliae density was 1.8-fold higher with ST than with MP (p = 0.018), but no differences were detected for RLN density between ST and MP. In the fall after the potato harvest, only two fields had significantly higher V. dahliae density with the ST than with MP, and no differences were detected for RLN density between ST and MP. When combined data across all fields were analyzed, no differences in pathogen population levels were detected between ST and MP for both V. dahliae and RLN. Higher PED severity was detected in three fields associated with ST. However, when disease ratings were averaged across all fields, no PED severity difference was detected between ST and MP. The PED severity was significantly positively related to the spring population density of V. dahliae and RLN, but not with the tillage regimes in this study. Further study is needed to determine the long-term effect of tillage regimes on soil health, disease development, soil disease suppressiveness, pathogen population dynamics and PED development in potato production.

Forest citizens and people‐centered conservation in the Brazilian Amazon - Luke Parry; Thiago F. Morello; James A. Fraser; Natalia Guerrero; Gabriela S. Lotta; Rodrigo C. Martins; Peter Newton; Jessica C. Pires Cardoso; Andreza A. Souza Santos; Mauricio Torres (Conservation Biology, 2025)
Demands for territorial recognition are foundational to the claiming of rights by forest‐proximate people who attempt to conserve their forests. The rights of these often‐marginalized populations have been largely overlooked by conservationists, yet they are central to achieving people‐centered conservation. We further developed the concept of forest citizenship as a normative framework and analytical tool based on Brazilian social environmentalism ( socioambientalismo ), florestania (a former political project in Acre state), Latin American scholarship on ecological citizenship, and Eurocentric political philosophy. Decades of struggle for territorial recognition and social inclusion have solidified the right to have rights for Amazonia's forest citizens. Hence, forest citizens are people who have become so through the sociopolitical dynamics of their rights claims. Forest citizenship is built on community mobilization to create legally recognized territories with participatory governance but becomes tangible only if individuals and communities can successfully claim other rights from institutions through everyday practices of citizenship. We also assessed the current number and distribution of forest citizens across Brazilian Amazonia based on gridded population data and spatial analyses to calculate the resident population in four territorial categories that meet these democratic preconditions: Indigenous lands, extractive reserves, sustainable development reserves, ecological settlement projects, and Afro‐descendent Quilombola territories. The territories covered 31% of the Legal Amazon, were home to 1.05 million forest citizens, and had diverse primary policy objectives but shared goals of empowering communities and conserving forests. To be emancipatory, forest citizenship must be bottom‐up, socially inclusive, and improve people's lives. We suggest that conservationists pay greater attention to power relations and decision‐making structures related to forest territories. Territory‐based forest citizenship may be relevant for other countries where environmentalism has intersected with struggles for land rights and democracy.

Bumble Bee Probability of Occurrence Responds to Interactions Between Local and Landscape Land Use, Climatic Niche Properties and Climate Change - Tim Newbold; Jeremy Kerr; Peter Soroye; Jessica J. Williams (Ecology Letters, 2025)
Insect biodiversity is changing rapidly, driven by a suite of pressures, notably land use, land‐use intensification and increasingly climate change. We lack large‐scale evidence on how land use and climate change interact to drive insect biodiversity changes. We assess bumble bee responses to interactive effects of land use and climate pressures across North America and Europe. The probability of occurrence increases in landscapes with a higher proportion of natural habitat and a shorter history of human disturbance. Responses to climate warming relative to historical conditions are weakly negative in natural habitats but positive in human land uses, while human land use reduces the probability of occurrence most in the centre of species' temperature niches. We estimate that the combined pressures have reduced bumble bee probability of occurrence by 44% across sampled natural habitats and 55% across human land uses, highlighting the pervasive influence that human pressures have had on biodiversity across habitats.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

Investigating suspended sediment dynamics in the Spöl and Inn rivers during experimental floods using high-resolution monitoring - Jessica Droujko; Jan Martini; Peter Molnar (Journal of Environmental Management, 2025)

Epidemiology of Coronavirus Disease 2019-Associated Fungal Infections in the Intensive Care Unit: A Single-Center Retrospective Study - Jessica S. Little; Gerald McGwin; Lisa Tushla; Kaitlin Benedict; Meghan M. Lyman; Mitsuru Toda; John W. Baddley; Peter G. Pappas (Mycopathologia, 2025)

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

Review of ecological valuation and equivalency analysis methods for assessing temperate nearshore submerged aquatic vegetation - Rachel E. Pausch; Jessica R. Hale; Peter Kiffney; Beth Sanderson; Sara Azat; Katie Barnas; W. Bryant Chesney; Natalie Cosentino‐Manning; Stephanie Ehinger; Dayv Lowry; Steve Marx (Conservation Biology, 2025)
Nearshore seagrass, kelp, and other macroalgae beds (submerged aquatic vegetation [SAV]) are productive and important ecosystems. Mitigating anthropogenic impacts on these habitats requires tools to quantify their ecological value and the debits and credits of impact and mitigation. To summarize and clarify the state of SAV habitat quantification and available tools, we searched peer‐reviewed literature and other agency documents for methods that either assigned ecological value to or calculated equivalencies between impact and mitigation in SAV. Out of 47 tools, there were 11 equivalency methods, 7 of which included a valuation component. The remaining valuation methods were most commonly designed for seagrasses and rocky intertidal macroalgae rather than canopy‐forming kelps. Tools were often designed to address specific resource policies and associated habitat evaluation. Frequent categories of tools and methods included those associated with habitat equivalency analyses and those that scored habitats relative to reference or ideal conditions, including models designed for habitat suitability indices and the European Union's Water and Marine Framework Directives. Over 29 tool input metrics spanned 3 spatial scales of SAV: individual shoots or stipes, bed or site, and landscape or region. The most common metric used for both seagrasses and macroalgae was cover. Seagrass tools also often employed density measures, and some categories used measures of tissue content (e.g., carbon, nitrogen). Macroalgal tools for rocky intertidal habitats frequently included species richness or incorporated indicator species to assess habitat. We provide a flowchart for decision‐makers to identify representative tools that may apply to their specific management needs.

A phylogenomic tree of wood-warblers (Aves: Parulidae): Dealing with good, bad, and ugly samples - Min Zhao; Jessica A. Oswald; Julie M. Allen; Hannah L. Owens; Peter A. Hosner; Robert P. Guralnick; Edward L. Braun; Rebecca T. Kimball (Molecular Phylogenetics and Evolution, 2025)

Stated preferences for the colours, smells, and sounds of biodiversity - Peter M. King; Martin Dallimer; Thomas Lundhede; Gail E. Austen; Jessica C. Fisher; Katherine N. Irvine; Robert D. Fish; Zoe G. Davies (Ecological Economics, 2025)

Testing the potential of zebularine to induce heritable changes in crop growth and development - E. Jean Finnegan; Peter A. Crisp; Peng Zhang; Judith Eglitis-Sexton; Julian Greenwood; Jessica Hintzsche; Jianbo Li; Jen Taylor; Xiaomei Wallace; Stephen Swain (Theoretical and Applied Genetics, 2025)
Key message Zebularine-treated wheat uncovered a phenotype with characteristics of an epigenetically regulated trait, but major chromosomal aberrations, not DNA methylation changes, are the cause, making zebularine unsuitable for epigenetic breeding. Abstract Breeding to identify disease-resistant and climate-tolerant high-yielding wheats has led to yield increases over many years, but new hardy, higher yielding varieties are still needed to improve food security in the face of climate change. Traditional breeding to develop new cultivars of wheat is a lengthy process taking more than seven years from the initial cross to cultivar release. The speed of breeding can be enhanced by using modern technologies including high-throughput phenomics, genomic selection, and directed mutation via CRISPR. Here we test the concept of modifying gene regulation by transiently disrupting DNA methylation with the methyltransferase inhibitor, zebularine (Zeb), as a means to uncover novel phenotypes in an elite cultivar to facilitate breeding for epigenetically controlled traits. The development and architecture of the wheat inflorescence, including spikelet density, are an important component of yield, and both grain size and number have been extensively modified during domestication and breeding of wheat cultivars. We identified several Zeb-treated plants with a dominant mutation that increased spikelet density compared to the untreated controls. Our analysis showed that in addition to causing loss of DNA methylation, Zeb treatment resulted in major chromosomal abnormalities, including trisomy and the formation of a novel telocentric chromosome. We provide evidence that increased copy number of the domestication gene, Q , is the most likely cause of increased spikelet density in two Zeb-treated plants. Collateral damage to chromosomes in Zeb-treated plants suggests that this is not a viable approach to epigenetic breeding.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Exploring the Nature of Arhopalus ferus (Coleoptera: Cerambycidae: Spondylidinae) Pheromone Attraction - Jessica L. Kerr; Cecilia M. Romo; Brooke O’Connor; Georgia Dickson; Max Novoselov; Samuel Aguilar-Arguello; Christine Todoroki; Adriana Najar-Rodriguez; Lee-Anne Manning; Andrew Twidle; Anne Barrington; Gaetan Leclair; et al. (Journal of Chemical Ecology, 2024)
Cerambycid species of the Spondylidinae subfamily are distributed worldwide and are known for being prolific invaders that infest conifers. In New Zealand, Arhopalus ferus (Mulsant), the burnt pine longhorn beetle, is well-established and requires monitoring at high-risk sites such as ports, airports, and sawmills as part of the requirements to meet pine log export standards set by the New Zealand Ministry of Primary Industries (MPI). Currently, its surveillance relies on traps baited with host volatiles (i.e., ethanol and α-pinene). We used volatile collections from adult beetles, electroantennograms, and field trapping bioassays to identify the pheromones emitted by the burnt pine longhorn beetle A. ferus and their effects on its behaviour. We show that A. ferus males emit mainly ( E )-fuscumol and geranylacetone, as well as the minor components, α -terpinene and p -mentha-1,3,8-triene, and that all four compounds elicit a dose-dependent response in antennae of both sexes. Traps baited with the binary combination of geranylacetone plus fuscumol captured significantly more female A. ferus than did unbaited traps in two of three field experiments. α-Terpinene did not affect A. ferus trap catches and effects of p -mentha-1,3,8-triene on trap catch were not determined. Our findings provide further evidence of the use of fuscumol and geranylacetone as aggregation-sex pheromones by longhorn beetles in the Spondylidinae subfamily, and suggest that their deployment in survey traps may improve the efficacy of A. ferus monitoring in New Zealand and elsewhere.

Private Woodland Owner Perceptions of Threat and Efficacy Shape Management Responses for Climate Change Adaptation - Peter Breigenzer; Jessica Leahy; Nicole Suzanne Rogers; Jay W Wason (Journal of Forestry, 2024)
Private woodland owners (PWOs) face an increasing number of considerations for climate change adaptation and mitigation activities in their forest management. Evidence suggests there may be a disconnect between PWOs’ climate change perceptions and behaviors, which can limit implementation. We conducted seventeen semistructured interviews in Maine to develop a typological framework of PWOs based on their perceptions of climate-induced threats and efficacy. Our results produced three types of PWOs: the steady-as-they-go landowner (low perceived threat), the science-driven landowner (high perceived threat; high efficacy), and the seeking-support landowner (high perceived threat; low efficacy). Although all three types of PWOs regularly implemented resistance and resilience practices, their attitudes toward transition practices (i.e., assisted migration) diverged based on their perceptions of threat and efficacy. This typological framework can be used when targeting communications to PWOs regarding the overlap between climate adaptive management and traditional best management practices. Study Implications: PWOs in our study recognized climate-related impacts while implementing diverse forest management practices to meet both climate-related and non-climate-related objectives. The divergent attitudes toward transition practices exhibited by our three PWO types highlight the notion that adaptive practices can be both intentional and incidental. Our findings suggest that outreach efforts should understand PWO perceptions of climate change threats and their feelings of efficacy in responding to such threats. When combined with knowledge about the overlap between traditional best management practices and new climate-adaptive strategies, extension and outreach efforts can tailor their messaging to fit the appropriate audience.

Microcosm experiment investigating climate-induced thermal effects on human virus viability in seawater: qPCR vs capsid integrity for enhanced risk management - Jessica L. Kevill; Xiaorong Li; Alvaro Garcia-Delgado; Kate Herridge; Kata Farkas; William Gaze; Peter Robins; Shelagh K. Malham; Davey L. Jones (Marine Pollution Bulletin, 2024)

Piloting wastewater-based surveillance of norovirus in England - David I. Walker; Jessica Witt; Wayne Rostant; Robert Burton; Vicki Davison; Jackie Ditchburn; Nicholas Evens; Reg Godwin; Jane Heywood; James A. Lowther; Nancy Peters; Jonathan Porter; et al. (Water Research, 2024)

Effects of Vibrio vulnificus and Microcystis aeruginosa co-exposures on microplastic accumulation and depuration in the Eastern Oyster (Crassostrea virginica) - Jessica T. Wenclawiak; John E. Weinstein; Peter B. Key; Craig J. Plante; Barbara A. Beckingham (Environmental Pollution, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Primary Non-Inversion Shallow Tillage Versus Moldboard Plowing Prior to Growing Potatoes: Short-Term Impacts on Potato Yield and Soil Properties in Eastern Canada - Judith Nyiraneza; Tandra D. Fraser; Danielle Murnaghan; Jessica Matheson; Stephanie Arnold; Kyra Stiles; Dahu Chen; Rick Peters; Mohammad Khakbazan; Ryan Barrett (American Journal of Potato Research, 2024)
Potato ( Solanum tuberosum L.) production often requires intensive tillage with the moldboard plow (MP), which involves deeper soil tillage and turning of the soil to provide enough loose soil for proper tuberization. Although tillage with the MP allows better potato seedbed preparation and lower weed pressure, it is also associated with increased soil compaction, soil aggregate destruction, and increased soil organic matter (SOM) mineralization. The objective of this four-year (2019–2022) study conducted in 14 commercial fields was to compare the use of MP with primary non-inversion shallow tillage (ST) in terms of their effect on selected soil health indicators, soil moisture, potato petiole nitrate concentration, potato yield, and specific gravity. Commercial fields ranged from 1.5 ha to 19 ha where the main field was split in half, with one side tilled using MP (22.5–30 cm plowing depth) and the other half using ST (15–30 cm plowing depth). Soil and plant tissue samples were taken within four sub-replicates (91 m 2 ) created per each treatment per each site and three to four sites were used as replicates per each year. Compared to MP, ST increased active carbon by an average of 9%, soil respiration by an average of 26%, and aggregate stability by an average of 8%. Biological N availability (BNA) increased by an average of 20% with ST, and the effect was statistically significant in three out of four years. Soil moisture at 20 cm depth tended to be higher with MP than ST in three out of four years. Although not statistically significant, when averaged across four years, potato petiole nitrate concentrations were 5% and 12% higher with ST than MP in samples collected at the flowering and post-potato flowering stages, respectively. Total and marketable potato yields, along with specific gravity, were comparable for the two tillage regimes. Signs of soil improvement were observed at the early stages of ST adoption. Marketable yield was negatively correlated with the soil nitrate levels measured during the growing season but was positively correlated with active carbon, aggregate stability, and soil moisture. Future studies could compare both tillage regimes over multiple growing seasons to assess their impacts over a full cycle of rotation. The novelty of the present study was that it was conducted in real-life conditions across large growers’ fields with different conditions and across four years.

A paleoenvironmental and ecological analysis of biomarkers from the Eocene Fossil Basin, Green River Formation, U.S.A. - Amy L. Elson; Lorenz Schwark; Jessica H. Whiteside; Peter Hopper; Stephen F. Poropat; Alex I. Holman; Kliti Grice (Organic Geochemistry, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Fostering effective and sustainable scientific collaboration and knowledge exchange: a workshop-based approach to establish a national ecological observatory network (NEON) domain-specific user group - Alison Donnelly; Ankur R. Desai; Katherine A. Heckman; Lucas E. Nave; Michael J. Cramer; Marie Faust; Peter Weishampel; Caleb Slemmons; Christian G. Andresen; Edward Ayres; Stacy R. Cotey; Kathryn M. Docherty; et al. (International Journal of Biometeorology, 2024)
The decision to establish a network of researchers centers on identifying shared research goals. Ecologically specific regions, such as the USA’s National Ecological Observatory Network’s (NEON’s) eco-climatic domains, are ideal locations by which to assemble researchers with a diverse range of expertise but focused on the same set of ecological challenges. The recently established Great Lakes User Group (GLUG) is NEON’s first domain specific ensemble of researchers, whose goal is to address scientific and technical issues specific to the Great Lakes Domain 5 (D05) by using NEON data to enable advancement of ecosystem science. Here, we report on GLUG’s kick off workshop, which comprised lightning talks, keynote presentations, breakout brainstorming sessions and field site visits. Together, these activities created an environment to foster and strengthen GLUG and NEON user engagement. The tangible outcomes of the workshop exceeded initial expectations and include plans for (i) two journal articles (in addition to this one), (ii) two potential funding proposals, (iii) an assignable assets request and (iv) development of classroom activities using NEON datasets. The success of this 2.5-day event was due to a combination of factors, including establishment of clear objectives, adopting engaging activities and providing opportunities for active participation and inclusive collaboration with diverse participants. Given the success of this approach we encourage others, wanting to organize similar groups of researchers, to adopt the workshop framework presented here which will strengthen existing collaborations and foster new ones, together with raising greater awareness and promotion of use of NEON datasets. Establishing domain specific user groups will help bridge the scale gap between site level data collection and addressing regional and larger ecological challenges.

White matter organisation of sensorimotor tracts is associated with motor imagery in childhood - Mugdha Mukherjee; Christian Hyde; Pamela Barhoun; Kaila M Bianco; Mervyn Singh; Jessica Waugh; Timothy J Silk; Jarrad AG Lum; Karen Caeyenberghs; Jacqueline Williams; Peter G Enticott; Ian Fuelscher (Brain Structure and Function, 2024)
Despite the important role of motor imagery (MI) in motor development, our understanding of the contribution of white matter fibre properties to MI performance in childhood remains limited. To provide novel insight into the white matter correlates of MI performance, this study examined the association between white matter fibre properties and motor imagery performance in a sample of typically developing children. High angular diffusion weighted imaging data were collected from 22 typically developing children aged 6–14 years (12 female, M Age = 10.56). Implicit motor imagery performance was assessed using a mental hand rotation paradigm. The cerebellar peduncles and the superior longitudinal fasciculus were reconstructed using TractSeg, a semi-automated method. For each tract, white matter microstructure (fibre density, FD) and morphology (fibre bundle cross-section, FC) were estimated using Fixel-Based Analysis. Permutation-based inference testing and partial correlation analyses demonstrated that higher FC in the middle cerebellar peduncles was associated with better MI performance. Tract-based region of interest analyses showed that higher FC in the middle and superior cerebellar peduncles were associated with better MI performance. Results suggest that white matter connectivity along the cerebellar peduncles may facilitate MI performance in childhood. These findings advance our understanding of the neurobiological systems that underlie MI performance in childhood and provide early evidence for the relevance of white matter sensorimotor pathways to internal action representations.

Interactive effects of fish handling and water temperature on reflex impairment of angled Rainbow Trout - Jessica A. Robichaud; Morgan L. Piczak; Luc LaRochelle; Jessica L. Reid; Auston D. Chhor; Peter E. Holder; Liane B. Nowell; Jacob W. Brownscombe; Andrew J. Danylchuk; Steven J. Cooke (Fisheries Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Effects of sea level rise and tidal flat growth on tidal dynamics and geometry of the Elbe estuary - Tara F. Mahavadi; Rita Seiffert; Jessica Kelln; Peter Fröhle (Ocean Science, 2024)
Future global mean sea level rise (SLR) will affect coastlines and estuaries in the North Sea and therefore also coastal protection structures, unique local ecosystems and important waterways. SLR will not only raise water levels but also influence tidal dynamics and morphodynamics, which is why the tidal flats of the Wadden Sea can grow to a certain extent with SLR. Investigations on the effects of climate-change-induced SLR and the related potential bathymetric changes inside of estuaries form an important basis for identifying vulnerabilities and developing appropriate adaptation strategies. To analyse the influence of potential SLR and tidal flat elevation scenarios on the tidal dynamics in the Elbe estuary, we used a highly resolved hydrodynamic numerical model of the German Bight. The analysis results show increasing tidal range in the Elbe estuary solely due to SLR. They also reveal strongly varying changes with different tidal flat growth scenarios: while tidal flat elevation up to the mouth of the estuary can cause tidal range to decrease relative to SLR alone, tidal flat elevation in the entire estuary can lead to an increase in tidal range relative to SLR alone. Further analyses show how the geometric parameters of the Elbe estuary are changing due to SLR and tidal flat elevation. We discuss how these changes in estuarine geometry can provide an explanation for the changes in tidal range.

Unravelling the fate of foliar-applied nickel in soybean: a comprehensive investigation - Jessica Bezerra de Oliveira; Jose Lavres; Peter M. Kopittke; Rufus L. Chaney; Hugh H. Harris; Peter D. Erskine; Daryl L. Howard; André Rodrigues dos Reis; Antony van der Ent (Plant and Soil, 2024)
Background and aims Nickel (Ni) deficiency has been reported to occur in soybean ( Glycine max ) grown on leached tropical soils in Brazil. We aimed to determine whether an internal or external Ni supply can compensate for low Ni within the seed by assessing whether the amount of Ni in the seed whether the foliar-application of aqueous NiSO 4 influenced the uptake of Ni by the leaf, the nutritional status of the plant, urease activity and growth. Methods We used Ni-depleted seeds (<0.35 μg Ni per g) and Ni-sufficient seeds (11.1 μg Ni g −1 ) for hydroponic experiments. Seedlings were grown either with or without an external Ni supply (0 or 0.85 μM Ni in nutrient solution) and either with or without an internal Ni supply (with or cotyledons removed). In addition, we used synchrotron-based micro-X-ray fluorescence analysis to examine the distribution of foliar-applied Ni (50 and 100 mg L -1 ). Key results Leaf Ni concentration and urease activity were both enhanced by increasing either the internal (cotyledon seed store) or external (solution) Ni supply. In addition, plants derived from Ni-depleted seed that received external Ni supply had 9.2% higher biomass relative to plants derived from Ni-sufficient seeds which received Ni. When foliar-applied, Ni accumulated in the pedicles of the trichomes within 15 minutes of application, and then moved to the vascular bundles before dispersing further into tissues within 3 hours. Conclusions Trichomes are an important pathway for foliar Ni absorption in soybean, but there are still major knowledge gaps our understanding of the physiological function of trichomes in the uptake of metal ions from foliar micro-nutrient treatments.

Seagrasses produce most of the soil blue carbon in three Maldivian islands - Peter I. Macreadie; Melissa Wartman; Philippa Roe; Jessica M. Hodge; Stephanie B. Helber; Pawel Waryszak; Vincent Raoult (Frontiers in Marine Science, 2024)
Blue carbon is fast garnering international interest for its disproportionate contribution to global carbon stocks. However, our understanding of the size of these blue carbon stocks, as well as the provenance of carbon that is stored within them, is still poor. This is especially pertinent for many small-island nations that may have substantial blue carbon ecosystems that are poorly studied. Here, we present a preliminary assessment of blue carbon from three islands in the Maldives. The higher purpose of this research was to assess the feasibility of using blue carbon to help offset carbon emissions associated with Maldivian tourism, the largest Maldivian industry with one of the highest destination-based carbon footprints, globally. We used stable isotope mixing models to identify how habitats contributed to carbon found in sediments, and Loss on Ignition (LoI) to determine carbon content. We found that for the three surveyed islands, seagrasses ( Thalassia hemprichii, Thalassodendron ciliatum, Halodule pinofilia, Syringodium isoetifolium , and Cymodocea rotundata ) were the main contributors to sediment blue carbon (55 – 72%) while mangroves had the lowest contribution (9 – 44%). Surprisingly, screw pine ( Pandanus spp.), a relative of palm trees found across many of these islands, contributed over a quarter of the carbon found in sediments. Organic carbon content (‘blue carbon’) was 6.8 ± 0.3 SE % and 393 ± 29 tonnes ha -1 for mangrove soils, and 2.5 ± 0.2% and 167 ± 20 tonnes ha -1 for seagrasses, which is slightly higher than global averages. While preliminary, our results highlight the importance of seagrasses as carbon sources in Maldivian blue carbon ecosystems, and the possible role that palms such as screw pines may have in supplementing this. Further research on Maldivian blue carbon ecosystems is needed to: 1) map current ecosystem extent and opportunities for additionality through conservation and restoration; 2) determine carbon sequestration rates; and 3) investigate options and feasibility for tourism-related blue carbon crediting. Overall, the opportunity for blue carbon in the Maldives is promising, but the state of knowledge is very limited.

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

Venous Thromboembolism: Review of Clinical Challenges, Biology, Assessment, Treatment, and Modeling - Connor Watson; Hicham Saaid; Vijay Vedula; Jessica C. Cardenas; Peter K. Henke; Franck Nicoud; Xiao Yun Xu; Beverley J. Hunt; Keefe B. Manning (Annals of Biomedical Engineering, 2024)

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Sediment analysis and historical context of the 2018 Palu-Donggala tsunami deposit, Indonesia - Jędrzej M. Majewski; Adam D. Switzer; Rachel Y.S. Guan; Benazir Benazir; Ella Meilianda; Peter R. Parham; Robert Weiss; Stacey S. Martin; Lillian K. Pearson; Jessica E. Pilarczyk; Patrick Daly; Benjamin P. Horton (Marine Geology, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

A Role for Visual Memory in Vocabulary Development: A Systematic Review and Meta-Analysis - Hayley E. Pickering; Jessica L. Peters; Sheila G. Crewther (Neuropsychology Review, 2023)
Although attention and early associative learning in preverbal children is predominantly driven by rapid eye-movements in response to moving visual stimuli and sounds/words (e.g., associating the word “bottle” with the object), the literature examining the role of visual attention and memory in ongoing vocabulary development across childhood is limited. Thus, this systematic review and meta-analysis examined the association between visual memory and vocabulary development, including moderators such as age and task selection, in neurotypical children aged 2-to-12 years, from the brain-based perspective of cognitive neuroscience. Visual memory tasks were classified according to the visual characteristics of the stimuli and the neural networks known to preferentially process such information, including consideration of the distinction between the ventral visual stream (processing more static visuo-perceptual details, such as form or colour) and the more dynamic dorsal visual stream (processing spatial temporal action-driven information). Final classifications included spatio-temporal span tasks, visuo-perceptual or spatial concurrent array tasks, and executive judgment tasks. Visuo-perceptual concurrent array tasks, reliant on ventral stream processing, were moderately associated with vocabulary, while tasks measuring spatio-temporal spans, associated with dorsal stream processing, and executive judgment tasks (central executive), showed only weak correlations with vocabulary. These findings have important implications for health professionals and researchers interested in language, as they advocate for the development of more targeted language learning interventions that include specific and relevant aspects of visual processing and memory, such as ventral stream visuo-perceptual details (i.e., shape or colour).

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)

Comparative compositions of grain of tritordeum, durum wheat and bread wheat grown in multi-environment trials - Peter R. Shewry; Fred Brouns; Jack Dunn; Jessica Hood; Amanda J. Burridge; Antoine H.P. America; Luud Gilissen; Zsuzsan A.M. Proos-Huijsmans; Jan Philip van Straaten; Daisy Jonkers; Paul A. Lazzeri; Jane L. Ward; et al. (Food Chemistry, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Questioning the business model of sustainable wine production: The case of French “Vallée du Rhône” wine growers - Jessica Lichy; Maher Kachour; Peter Stokes (Journal of Cleaner Production, 2023)

Correction to: Prioritizing river basins for intensive monitoring and assessment by the US Geological Survey - Peter C. Van Metre; Sharon Qi; Jeffrey Deacon; Cheryl Dieter; Jessica M. Driscoll; Michael Fienen; Terry Kenney; Patrick Lambert; David Lesmes; Christopher A. Mason; Anke Mueller-Solger; Marylynn Musgrove; et al. (Environmental Monitoring and Assessment, 2023)

Expression in skin biopsies supports genetic evidence linking CAMKK2, P2X7R and P2X4R with HIV-associated sensory neuropathy - Jessica Gaff; Fitri Octaviana; Connie Jackaman; Peter Kamerman; John Papadimitriou; Silvia Lee; Jenjira Mountford; Patricia Price (Journal of NeuroVirology, 2023)
HIV-associated sensory neuropathy (HIV-SN) affects 14–38% of HIV+ individuals stable on therapy with no neurotoxic drugs. Polymorphisms in CAMKK2 , P2X7R and P2X4R associated with altered risk of HIV-SN in Indonesian and South African patients. The role of CaMKK2 in neuronal repair makes this an attractive candidate, but a direct role for any protein is predicated on expression in affected tissues. Here, we describe expression of CaMKK2, P2X7R and P2X4R proteins in skin biopsies from the lower legs of HIV+ Indonesians with and without HIV-SN, and healthy controls (HC). HIV-SN was diagnosed using the Brief Peripheral Neuropathy Screen. Biopsies were stained to detect protein gene product 9.5 on nerve fibres and CaMKK2, P2X7R or P2X4R, and were examined using 3-colour sequential scanning confocal microscopy. Intraepidermal nerve fibre densities (IENFD) were lower in HIV+ donors than HC and correlated directly with nadir CD4 T-cell counts ( r = 0.69, p = 0.004). However, IENFD counts were similar in HIV-SN+ and HIV-SN− donors ( p = 0.19) and so did not define neuropathy. CaMKK2+ cells were located close to dermal and epidermal nerve fibres and were rare in HC and HIV-SN− donors, consistent with a role for the protein in nerve damage and/or repair. P2X7R was expressed by cells in blood vessels of HIV-SN− donors, but rarely in HC or HIV-SN+ donors. P2X4R expression by cells in the epidermal basal layer appeared greatest in HIV-SN+ donors. Overall, the differential expression of CaMKK2, P2X7R and P2X4R supports the genetic evidence of a role for these proteins in HIV-SN.

Dynamic emergent leaf area in tidal wetlands: Implications for satellite-derived regional and global blue carbon estimates - Peter A. Hawman; Deepak R. Mishra; Jessica L. O'Connell (Remote Sensing of Environment, 2023)

Resolving the masculinity dilemma: Identifying subtypes of male meat consumers with latent profile analysis - Lauren Camilleri; Peter Richard Gill; Jessica Scarfo; Andrew Jago (Food Quality and Preference, 2023)

Greenness modifies the association between ambient air pollution and cognitive function in Australian adolescents, but not in mid-life adults - Yichao Wang; Mallery Crowe; Luke D. Knibbs; Matthew Fuller-Tyszkiewicz; Lærke Mygind; Jessica A. Kerr; Melissa Wake; Craig A. Olsson; Peter G. Enticott; Rachel L. Peters; Galina Daraganova; Suzanne Mavoa; et al. (Environmental Pollution, 2023)

Years late and millions short: A predictive audit of economic impacts for coal mines in British Columbia, Canada - Rosemary Collard; Jessica Dempsey; Bruce Muir; Robyn Allan; Abigail Herd; Peter Bode (Environmental Impact Assessment Review, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Polygenic routes lead to parallel altitudinal adaptation in Heliosperma pusillum (Caryophyllaceae) - Aglaia Szukala; Jessica Lovegrove‐Walsh; Hirzi Luqman; Simone Fior; Thomas M. Wolfe; Božo Frajman; Peter Schönswetter; Ovidiu Paun (Molecular Ecology, 2023)
Understanding how organisms adapt to the environment is a major goal of modern biology. Parallel evolution—the independent evolution of similar phenotypes in different populations—provides a powerful framework to investigate the evolutionary potential of populations, the constraints of evolution, its repeatability and therefore its predictability. Here, we quantified the degree of gene expression and functional parallelism across replicated ecotype formation in Heliosperma pusillum (Caryophyllaceae), and gained insights into the architecture of adaptive traits. Population structure analyses and demographic modelling support a previously formulated hypothesis of parallel polytopic divergence of montane and alpine ecotypes. We detect a large proportion of differentially expressed genes (DEGs) underlying divergence within each replicate ecotype pair, with a strikingly low number of shared DEGs across pairs. Functional enrichment of DEGs reveals that the traits affected by significant expression divergence are largely consistent across ecotype pairs, in strong contrast to the nonshared genetic basis. The remarkable redundancy of differential gene expression indicates a polygenic architecture for the diverged adaptive traits. We conclude that polygenic traits appear key to opening multiple routes for adaptation, widening the adaptive potential of organisms.

Reliability and Validity of Digital Images to Assess Child Dietary Intake in a Quick-Service Restaurant Setting - Eleanor T. Shonkoff; Erin Hennessy; Ken Chui; Julie E. Gervis; Emilia Matthews; Sarah Amin; Peter Bakun; Susan B. Roberts; Michelle Borges; Jessica Martino; Christina D. Economos (Journal of the Academy of Nutrition and Dietetics, 2023)

Stepping up to genome scan allows stock differentiation in the worldwide distributed blue shark Prionace glauca - Natacha Nikolic; Floriaan Devloo‐Delva; Diane Bailleul; Ekaterina Noskova; Clément Rougeux; Chrystelle Delord; Philippe Borsa; Cathy Liautard‐Haag; Mohamad Hassan; Amandine D. Marie; Pierre Feutry; Peter Grewe; et al. (Molecular Ecology, 2023)
The blue shark Prionace glauca is a top predator with one of the widest geographical distributions of any shark species. It is classified as Critically Endangered in the Mediterranean Sea, and Near Threatened globally. Previous genetic studies did not reject the null hypothesis of a single global population. The blue shark was proposed as a possible archetype of the “grey zone of population differentiation,” coined to designate cases where population structure may be too recent or too faint to be detected using a limited set of markers. Here, blue shark samples collected throughout its global range were sequenced using a specific RAD method (DArTseq), which recovered 37,655 genome‐wide single nucleotide polymorphisms (SNPs). Two main groups emerged, with Mediterranean Sea and northern Atlantic samples (Northern population) differentiated significantly from the Indo‐west Pacific samples (Southern population). Significant pairwise F ST values indicated further genetic differentiation within the Atlantic Ocean, and between the Atlantic Ocean and the Mediterranean Sea. Reconstruction of recent demographic history suggested divergence between Northern and Southern populations occurred about 500 generations ago and revealed a drastic reduction in effective population size from a large ancestral population. Our results illustrate the power of genome scans to detect population structure and reconstruct demographic history in highly migratory marine species. Given that the management plans of the blue shark (targeted or bycatch) fisheries currently assume panmictic regional stocks, we strongly recommend that the results presented here be considered in future stock assessments and conservation strategies.

Constraining the composition and quantity of organic matter used by abundant marine Thaumarchaeota - Alma E. Parada; Xavier Mayali; Peter K. Weber; Jessica Wollard; Alyson E. Santoro; Jed A. Fuhrman; Jennifer Pett‐Ridge; Anne E. Dekas (Environmental Microbiology, 2023)
Marine Group I (MGI) Thaumarchaeota were originally described as chemoautotrophic nitrifiers, but molecular and isotopic evidence suggests heterotrophic and/or mixotrophic capabilities. Here, we investigated the quantity and composition of organic matter assimilated by individual, uncultured MGI cells from the Pacific Ocean to constrain their potential for mixotrophy and heterotrophy. We observed that most MGI cells did not assimilate carbon from any organic substrate provided (glucose, pyruvate, oxaloacetate, protein, urea, and amino acids). The minority of MGI cells that did assimilate it did so exclusively from nitrogenous substrates (urea, 15% of MGI and amino acids, 36% of MGI), and only as an auxiliary carbon source (

Long-term aircraft noise exposure and risk of hypertension in postmenopausal women - Daniel D. Nguyen; Eric A. Whitsel; Gregory A. Wellenius; Jonathan I. Levy; Jessica H. Leibler; Stephanie T. Grady; James D. Stewart; Matthew P. Fox; Jason M. Collins; Melissa N. Eliot; Andrew Malwitz; JoAnn E. Manson; et al. (Environmental Research, 2023)

A cultivar phenology classification scheme for wheat and barley - Corinne Celestina; James Hunt; Haydn Kuchel; Felicity Harris; Kenton Porker; Ben Biddulph; Maxwell Bloomfield; Melissa McCallum; Rick Graham; Peter Matthews; Darren Aisthorpe; Ghazwan Al-Yaseri; et al. (European Journal of Agronomy, 2023)

Outdoor light at night and risk of endometrial cancer in the NIH-AARP diet and health study - Danielle N. Medgyesi; Britton Trabert; Jared A. Fisher; Qian Xiao; Peter James; Alexandra J. White; Jessica M. Madrigal; Rena R. Jones (Cancer Causes & Control, 2023)

Mainstreaming germline genetic testing for patients with pancreatic cancer increases uptake - Mitchell L. Ramsey; Jewel Tomlinson; Rachel Pearlman; Laith Abushahin; Amber Aeilts; Hui-Zi Chen; Yan Chen; Ashley Compton; Rifat Elkhatib; Levi Geiger; John Hays; Joanne Jeter; et al. (Familial Cancer, 2023)

Fatty acid profiles of more than 470 marine species from the Southern Hemisphere - Peter D. Nichols; Heidi R. Pethybridge; Bowen Zhang; Patti Virtue; Lauren Meyer; Zahirah Dhurmeea; Lara Marcus; Jessica A. Ericson; Nicole Hellessey; Sharon Every; Kathryn Wheatley; Christopher C. Parrish; et al. (Ecology, 2023)
Lipid and fatty acid datasets are commonly used to assess the nutritional composition of organisms, trophic ecology, and ecosystem dynamics. Lipids and their fatty acid constituents are essential nutrients to all forms of life because they contribute to biological processes such as energy flow and metabolism. Assessment of total lipids in tissues of organisms provides information on energy allocation and life‐history strategies and can be an indicator of nutritional condition. The analysis of an organism's fatty acids is a widely used technique for assessing nutrient and energy transfer, and dietary interactions in food webs. Although there have been many published regional studies that assessed lipid and fatty acid compositions, many only report the mean values of the most abundant fatty acids. There are limited individual records available for wider use in intercomparison or macro‐scale studies. This dataset consists of 4856 records of individual and pooled samples of at least 470 different marine consumer species sampled from tropical, temperate, and polar regions around Australia and in the Southern, Indian, and Pacific Oceans from 1989 to 2018. This includes data for a diverse range of taxa (zooplankton, fish, cephalopods, chondrichthyans, and marine mammals), size ranges (0.02 cm to ~13 m), and that cover a broad range of trophic positions (2.0–4.6). When known, we provide a record of species name, date of sampling, sampling location, body size, relative (%) measurements of tissue‐specific total lipid content and abundant fatty acids, and absolute content (mg 100 g −1 tissue) of eicosapentaenoic acid (EPA, 20:5n3) and docosahexaenoic acid (DHA, 22:6n3) as important long‐chain (≥C 20 ) polyunsaturated omega‐3 fatty acids. These records form a solid basis for comparative studies that will facilitate a broad understanding of the spatial and temporal distribution of marine lipids globally. The dataset also provides reference data for future dietary assessments of marine predators and model assessments of potential impacts of climate change on the availability of marine lipids and fatty acids. There are 480 data records within our data file for which the providers have requested that permission for reuse be granted, with the likely condition that they are included as a coauthor on the reporting of the dataset. Records with this condition are indicated by a “yes” under “Conditions_of_data_use” in Data S1: Marineconsumer_FAdata.csv (see Table 2 in Metadata S1 for more details). For all other data records marked as “No” under “Conditions_of_data_use,” there are no copyright restrictions for research and/or teaching purposes. We request that users acknowledge use of the data in publications, research proposals, websites, and other outlets via formal citation of this work and original data sources as applicable.

Characteristics of extreme daily precipitation events over the Canadian Arctic - Mark C. Serreze; Jessica Voveris; Andrew P. Barrett; Shari Fox; Peter D. Blanken; Alex Crawford (International Journal of Climatology, 2022)
Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Developing a Dedicated Leadership Curriculum for Radiation Oncology Residents - Ethan Y. Song; Jessica Chuang; Jessica M. Frakes; Thomas Dilling; Joann F. Quinn; Stephen Rosenberg; Peter Johnstone; Louis Harrison; Sarah E. Hoffe (Journal of Cancer Education, 2022)

Low-Cost, Deep-Sea Imaging and Analysis Tools for Deep-Sea Exploration: A Collaborative Design Study - Katherine L. C. Bell; Jennifer Szlosek Chow; Alexis Hope; Maud C. Quinzin; Kat A. Cantner; Diva J. Amon; Jessica E. Cramp; Randi D. Rotjan; Lehua Kamalu; Asha de Vos; Sheena Talma; Salome Buglass; et al. (Frontiers in Marine Science, 2022)
A minuscule fraction of the deep sea has been scientifically explored and characterized due to several constraints, including expense, inefficiency, exclusion, and the resulting inequitable access to tools and resources around the world. To meet the demand for understanding the largest biosphere on our planet, we must accelerate the pace and broaden the scope of exploration by adding low-cost, scalable tools to the traditional suite of research assets. Exploration strategies should increasingly employ collaborative, inclusive, and innovative research methods to promote inclusion, accessibility, and equity to ocean discovery globally. Here, we present an important step toward this new paradigm: a collaborative design study on technical capacity needs for equitable deep-sea exploration. The study focuses on opportunities and challenges related to low-cost, scalable tools for deep-sea data collection and artificial intelligence-driven data analysis. It was conducted in partnership with twenty marine professionals worldwide, covering a broad representation of geography, demographics, and domain knowledge within the ocean space. The results of the study include a set of technical requirements for low-cost deep-sea imaging and sensing systems and automated image and data analysis systems. As a result of the study, a camera system called Maka Niu was prototyped and is being field-tested by thirteen interviewees and an online AI-driven video analysis platform is in development. We also identified six categories of open design and implementation questions highlighting participant concerns and potential trade-offs that have not yet been addressed within the scope of the current projects but are identified as important considerations for future work. Finally, we offer recommendations for collaborative design projects related to the deep sea and outline our future work in this space.

Essential tremor impairs the ability to suppress involuntary action impulses - Jessi M. Kane; Jessica L. McDonnell; Joseph S. Neimat; Peter Hedera; Wery P. M. van den Wildenberg; Fenna T. Phibbs; Elise B. Bradley; Scott A. Wylie; Nelleke C. van Wouwe (Experimental Brain Research, 2022)

Regional diet in Antarctic krill (Euphausia superba) as determined by lipid, fatty acid, and sterol composition - Nicole Hellessey; Jessica A. Ericson; Peter D. Nichols; So Kawaguchi; Stephen Nicol; Nils Hoem; Patti Virtue (Polar Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Population genetic structure of a major reef-building coral species Acropora downingi in northeastern Arabian Peninsula - Felipe Torquato; Jessica Bouwmeester; Pedro Range; Alyssa Marshell; Mark A. Priest; John A. Burt; Peter R. Møller; Radhouan Ben-Hamadou (Coral Reefs, 2022)
Current seawater temperatures around the northeastern Arabian Peninsula resemble future global forecasts as temperatures > 35 °C are commonly observed in summer. To provide a more fundamental aim of understanding the structure of wild populations in extreme environmental conditions, we conducted a population genetic study of a widespread, regional endemic table coral species, Acropora downingi , across the northeastern Arabian Peninsula. A total of 63 samples were collected in the southern Arabian/Persian Gulf (Abu Dhabi and Qatar) and the Sea of Oman (northeastern Oman). Using RAD-seq techniques, we described the population structure of A. downingi across the study area. Pairwise G’st and distance-based analyses using neutral markers displayed two distinct genetic clusters: one represented by Arabian/Persian Gulf individuals, and the other by Sea of Oman individuals. Nevertheless, a model-based method applied to the genetic data suggested a panmictic population encompassing both seas. Hypotheses to explain the distinctiveness of phylogeographic subregions in the northeastern Arabian Peninsula rely on either (1) bottleneck events due to successive mass coral bleaching, (2) recent founder effect, (3) ecological speciation due to the large spatial gradients in physical conditions, or (4) the combination of seascape features, ocean circulation and larval traits. Neutral markers indicated a slightly structured population of A. downingi, which exclude the ecological speciation hypothesis . Future studies across a broader range of organisms are required to furnish evidence for existing hypotheses explaining a population structure observed in the study area. Though this is the most thermally tolerant acroporid species worldwide, A. downingi corals in the Arabian/Persian Gulf have undergone major mortality events over the past three decades. Therefore, the present genetic study has important implications for understanding patterns and processes of differentiation in this group, whose populations may be pushed to extinction as the Arabian/Persian Gulf warms.

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Tree diversity effects on soil microbial biomass and respiration are context dependent across forest diversity experiments - Simone Cesarz; Dylan Craven; Harald Auge; Helge Bruelheide; Bastien Castagneyrol; Jessica Gutknecht; Andy Hector; Hervé Jactel; Julia Koricheva; Christian Messier; Bart Muys; Michael J. O’Brien; et al. (Global Ecology and Biogeography, 2022)
Aim Soil microorganisms are essential for the functioning of terrestrial ecosystems. Although soil microbial communities and functions are linked to tree species composition and diversity, there has been no comprehensive study of the generality or context dependence of these relationships. Here, we examine tree diversity–soil microbial biomass and respiration relationships across environmental gradients using a global network of tree diversity experiments. Location Boreal, temperate, subtropical and tropical forests. Time period 2013. Major taxa studied Soil microorganisms. Methods Soil samples collected from 11 tree diversity experiments were used to measure microbial respiration, biomass and respiratory quotient using the substrate‐induced respiration method. All samples were measured using the same analytical device, method and procedure to reduce measurement bias. We used linear mixed‐effects models and principal components analysis (PCA) to examine the effects of tree diversity (taxonomic and phylogenetic), environmental conditions and interactions on soil microbial properties. Results Abiotic drivers, mainly soil water content, but also soil carbon and soil pH, significantly increased soil microbial biomass and respiration. High soil water content reduced the importance of other abiotic drivers. Tree diversity had no effect on the soil microbial properties, but interactions with phylogenetic diversity indicated that the effects of diversity were context dependent and stronger in drier soils. Similar results were found for soil carbon and soil pH. Main conclusions Our results indicate the importance of abiotic variables, especially soil water content, for maintaining high levels of soil microbial functions and modulating the effects of other environmental drivers. Planting tree species with diverse water‐use strategies and structurally complex canopies and high leaf area might be crucial for maintaining high soil microbial biomass and respiration. Given that greater phylogenetic distance alleviated unfavourable soil water conditions, reforestation efforts that account for traits improving soil water content or select more phylogenetically distant species might assist in increasing soil microbial functions.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Subsurface Microbial Community Composition in Anchialine Environments Is Influenced by Original Organic Carbon Source at Time of Deposition - Catherine A. Risley; Anne E. Tamalavage; Peter J. van Hengstum; Jessica M. Labonté (Frontiers in Marine Science, 2022)
Prokaryotes constitute the majority of sedimentary biomass, where they cycle organic carbon and regulate organic matter transformation. The microbes inhabiting sediment are diverse and the factors controlling microbial community composition are not fully understood. Here, we characterized the prokaryotic community using 16S rRNA gene sequencing in 24 stratigraphic layers within a 89 cm (dated to ~1900 years old) sediment core from an anchialine sinkhole in the Bahamas with a stratified water column and anoxic bottom water. The microbial community was dominated by members of the Alphaproteobacteria, Dehalococcoidia, Gammaproteobacteria, Bathyarchaeota, and Campylobacter classes. Most interestingly, subsurface microbial community structure could be correlated to previous evidence for timewise changes in the main source of organic matter that was supplied to the sediment accumulating during the last 2000 years, which itself was caused by regional terrestrial vegetation changes. The C:N ratio was correlated to the relative abundance of the microbial classes, and the microbial communities followed three previously determined time periods based on the source of organic matter, which suggests that the carbon source at time of deposition influences the resultant subsurface microbial community composition. These results show that carbon source is a driver of the microbial community composition inhabiting anoxic sediment, which could have implications for improving understanding of carbon cycling in coastal sedimentary basins.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Emergency department testing is feasible but ineffective to eliminate hepatitis C in Denmark - Jessica Jennifer Wentworth; Anne Lindebo Holm Øvrehus; Janne Fulgsang Hansen; Peter Biesenbach; Peer Brehm Christensen (Infectious Diseases, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Homogeneity of cognitive and behavioural processes underlying the relationship between insomnia and body image disturbance - Umair Akram; Sarah F. Allen; Jodie C. Stevenson; Lambros Lazuras; Millicent Ackroyd; Jessica Chester; Jessica Longden; Chloe Peters; Kamila R. Irvine (Cognitive Processing, 2021)
Specific cognitive behavioural mechanisms related to selective attention, situational avoidance and physical appearance are implicated in the development and maintenance of insomnia and negative reinforcement of body image disturbances. Therefore, we examined whether these processes potentially mediate the relationship between insomnia and body image perception. N = 728 participants completed self-reported measures of sleep-associated monitoring, insomnia symptoms, body image disturbance and coping with body image challenges. Symptoms of insomnia and sleep-associated monitoring behaviour were independently related to increased reports of body image disturbance, cognitive distortions of body image, appearance fixing (i.e. altering appearance by covering, camouflaging or correcting the perceived defect), avoidance (i.e. attempt to escape or avert stressful body image situations) and reduced levels of positive rationale acceptance (i.e. acceptance of the challenging event and positive self-care or rationale self-talk about one’s appearance). More crucially, sleep-related monitoring on awakening, cognitive distortion of body image and negative coping strategies related to body image (i.e. appearance fixing, avoidance, rationale acceptance) mediated the relationship between reports of body image disturbance and insomnia symptoms. The current findings expand upon previous research demonstrating consistent relationships between poor sleep and increased dissatisfaction with cutaneous features, by providing novel evidence that body image disturbances are associated with symptoms of insomnia. More crucially, we highlight the role of particular cognitive and behavioural mechanisms pertaining to sleep (i.e. selective attention for physical signs of poor sleep) and body image (i.e. avoidance and rationale acceptance) which may be targeted as part of cognitive behavioural treatments.

University of Washington Nathan Shock Center: innovation to advance aging research - Matt Kaeberlein; Alessandro Bitto; Maitreya J. Dunham; Warren Ladiges; Su-In Lee; Michael J. MacCoss; Alexander Mendenhall; Daniel E. L. Promislow; Peter S. Rabinovitch; Judit Villén; Lu Wang; Yuliang Wang; et al. (GeroScience, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Opening a Marine Monument to Commercial Fishing Compromises Species Protections - Jessica V. Redfern; Kelly A. Kryc; Lena Weiss; Brooke C. Hodge; Orfhlaith O’Brien; Scott D. Kraus; Ester Quintana-Rizzo; Peter J. Auster (Frontiers in Marine Science, 2021)
One of today’s greatest conservation challenges is balancing policies, laws, and management strategies established to achieve economic goals that depend on extracting ocean resources with those established to conserve marine biodiversity. We use the Northeast Canyons and Seamounts Marine National Monument (NCSM) as a case study to explore the consequences of changing from a policy that prevents fishing to a fisheries management policy. We found that opening the NCSM to commercial fishing reduces species protections. Fishing with pelagic and bottom tending fixed gear exposes species inhabiting the sea surface and midwater regions to entanglement and bycatch risk. Fishing with bottom tending fixed gear also exposes deep-sea coral habitat to gear known to have detrimental impacts. The NCSM was designated as a marine national monument due to the area’s unique ecological resources that are a subject of scientific interest. Our case study demonstrates that a fisheries management policy is insufficient to protect these ecological resources.

Correction to: From facilitation to competition: the effect of black locust (Robinia pseudoacacia L.) on the growth performance of four poplar-hybrids (Populus spp.) in mixed short rotation coppice - Jessica Rebola‑Lichtenberg; Juliane Streit; Peter Schall; Christian Ammer; Dominik Seidel (New Forests, 2021)

From facilitation to competition: the effect of black locust (Robinia pseudoacacia L.) on the growth performance of four poplar-hybrids (Populus spp.) in mixed short rotation coppice - Jessica Rebola-Lichtenberg; Juliane Streit; Peter Schall; Christian Ammer; Dominik Seidel (New Forests, 2021)
Short rotation coppices play an important role in providing biomass for energetic use. Mixing fast-growing tree species in short rotation coppices may show complementarity effects and increased yield. The aim of this study was to analyze the effect of species interaction in mixed short rotation coppices with fast-growing Populus spp.-hybrids and the N-fixing Robinia pseudoacacia . Four different Populus -hybrids (AF2, Fritzi Pauley, Hybride 275 and Max 1), planted alternately in pure and mixed stands with R. pseudoacacia were used for the analysis. Height and root collar diameter were measured once a year, over a period of four years (2014–2017). Additionally, in the third year, aboveground competition was surveyed with a terrestrial laser scanner and root biomass was analyzed to assess belowground competition. Soil nitrogen was also determined in order to verify enrichment properties of mixtures compared to pure stands. Populus -hybrids’ stem volume showed no significant differences between stand types in the first year after planting. In the second and third year, however, two Populus -hybrids (AF2 and Max 1) had a higher stem volume increment of up to 3.8 times than stem volume increment in pure stands. This may be related to the fact that soil nitrogen was 39% higher in the mixtures than in pure stands. However, in the 4th year after stand establishment, R. pseudoacacia’s crowns were so massive and broad, that this species was far more competitive than the Populus -hybrids. With the exception of P. ‘Fritzi Pauley’, which showed no significant differences between stand types, growth rates reversed for the other three Populus -hybrids. AF2, Max 1 and Hybride 275 showed up to 75% lower stem volume increment in mixtures compared to pure stands. We assume that, in spite of the initially observed facilitation between the species, the competition exerted by R. pseudoacacia started dominating after 4 years and began to surpass the benefits of facilitation.

Spatial Variation in Pelagic Wildlife Assemblages in the Ascension Island Marine Protected Area: Implications for Monitoring and Management - Christopher D. H. Thompson; Jessica J. Meeuwig; Judith Brown; Andrew J. Richardson; Alan M. Friedlander; Peter I. Miller; Sam B. Weber (Frontiers in Marine Science, 2021)
Bathymetric features such as islands and seamounts, as well as dynamic ocean features such as fronts often harbour rich marine communities. We deployed mid-water baited remote underwater video systems on three expeditions in Ascension Island’s Exclusive Economic Zone (EEZ), surveying the waters associated with six different bathymetric and dynamic ocean features: Ascension Island, two shallow seamounts (summits ≤ 101 m), one deeper seamount (summit > 250 m), apparent fronts, and haphazardly sampled open ocean areas. At Ascension Island, the pelagic assemblage consisted of a moderate proportion of predators and a diverse range of other taxa, including turtles, dolphins, and large non-piscivores. At the two shallow seamounts, sharks, tunas, billfish, and other large pelagic predators formed the vast majority of the assemblage, contributing > 99.9% of biomass and > 86% of abundance. At the deeper seamount, the pelagic community was comparatively depauperate, however the functional composition of its assemblage indicated some similarities to the shallow seamounts. Apparent fronts did not significantly differ from random offshore sites for metrics such as total abundance and taxonomic richness. However, they harboured assemblages with more abundant sharks, tunas, and large piscivores than random ocean open locations and these differences may be driven by certain front-associated species. Our results illustrate that pelagic assemblages vary markedly among different physical and oceanographic features and that seamounts appear particularly important for pelagic predators. The diversity and abundance of the assemblage, as well as the threatened status of many of the species observed, serve to highlight the conservation value of the Ascension Island EEZ. Our results also provide important baseline information of pelagic wildlife assemblages against which the performance of the recently implemented Ascension Island Marine Protected Area can be evaluated.

Time to rethink trophic levels in aquaculture policy - Richard S. Cottrell; Marc Metian; Halley E. Froehlich; Julia L. Blanchard; Nis Sand Jacobsen; Peter B. McIntyre; Kirsty L. Nash; David R. Williams; Lex Bouwman; Jessica A. Gephart; Caitlin D. Kuempel; Daniel D. Moran; et al. (Reviews in Aquaculture, 2021)
Aquaculture policy often promotes production of low‐trophic level species for sustainable industry growth. Yet, the application of the trophic level concept to aquaculture is complex, and its value for assessing sustainability is further complicated by continual reformulation of feeds. The majority of fed farmed fish and invertebrate species are produced using human‐made compound feeds that can differ markedly from the diet of the same species in the wild and continue to change in composition. Using data on aquaculture feeds, we show that technical advances have substantially decreased the mean effective trophic level of farmed species, such as salmon (mean TL = 3.48 to 2.42) and tilapia (2.32 to 2.06), from 1995 to 2015. As farmed species diverge in effective trophic level from their wild counterparts, they are coalescing at a similar effective trophic level due to standardisation of feeds. This pattern blurs the interpretation of trophic level in aquaculture because it can no longer be viewed as a trait of the farmed species, but rather is a dynamic feature of the production system. Guidance based on wild trophic position or historical resource use is therefore misleading. Effective aquaculture policy needs to avoid overly simplistic sustainability indicators such as trophic level. Instead, employing empirically derived metrics based on the specific farmed properties of species groups, management techniques and advances in feed formulation will be crucial for achieving truly sustainable options for farmed seafood.

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

Ghosts of the deep – Biodiversity, fisheries, and extinction risk of ghost sharks - Brittany Finucci; Jessica Cheok; David A. Ebert; Katelyn Herman; Peter M. Kyne; Nicholas K. Dulvy (Fish and Fisheries, 2021)
Ghost sharks (subclass Holocephali) remain a largely data‐poor group of cartilaginous fishes. The general paucity of attention may partially be related to identification and unresolved taxonomic issues, occurrence in the deep oceans, and their low value and interest in fisheries (which some notable exceptions). Here, we synthesize and assess the extinction risk of all known extant ghost sharks (52 species) by applying the IUCN Red List of Threatened Species Categories and Criteria. Ghost sharks have a low proportion of threatened (8%) and Near Threatened (8%) species, with most species (69%) assessed as Least Concern. The group still exhibits some data deficiency (15%), and biological information is lacking for most species. Endemism is high, with 37% of species known from only one location or one country. Species richness was highest in the Northeast Atlantic, off the northwest coast of Africa (Morocco to Mauritania), the East China Sea, New Zealand and off the northwest coast of South America (Ecuador and Peru). Ghost sharks are predominately taken as by‐catch, but some targeted fishing and/or retention for the liver oil trade occurs. Species‐specific reporting, monitoring and management are required to assess population trends, and further investigation is needed on trade and use, particularly for higher risk species including the sicklefin chimaeras (genus Neoharriotta ) and the American Elephantfish ( Callorhynchus callorhynchus , Callorhinidae).

Key competencies in sustainability in higher education—toward an agreed-upon reference framework - Katja Brundiers; Matthias Barth; Gisela Cebrián; Matthew Cohen; Liliana Diaz; Sonya Doucette-Remington; Weston Dripps; Geoffrey Habron; Niki Harré; Meghann Jarchow; Kealalokahi Losch; Jessica Michel; et al. (Sustainability Science, 2021)

Nutrition and growth outcomes are affected by aflatoxin exposures in Kenyan children - Ruth Nabwire Wangia-Dixon; Kathy Siyu Xue; Jessica Alcala; Trang Ho Thu Quach; Xiao Song; Lili Tang; James Ombaka; David Peter Githanga; Omu Aggrey Anzala; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2020)

Length–weight relationships to quantify biomass for motile coral reef cryptofauna - Kennedy Wolfe; Amelia Desbiens; Jessica Stella; Peter J. Mumby (Coral Reefs, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Polycyclic aromatic hydrocarbons (PAHs) and putative PAH-degrading bacteria in Galveston Bay, TX (USA), following Hurricane Harvey (2017) - Hernando P. Bacosa; Jamie Steichen; Manoj Kamalanathan; Rachel Windham; Arnold Lubguban; Jessica M. Labonté; Karl Kaiser; David Hala; Peter H. Santschi; Antonietta Quigg (Environmental Science and Pollution Research, 2020)

Uptake and Biological Effects of Perfluorooctane Sulfonate Exposure in the Adult Eastern Oyster Crassostrea virginica - Allisan A. Aquilina-Beck; Jessica L. Reiner; Katy W. Chung; Meaghan J. DeLise; Peter B. Key; Marie E. DeLorenzo (Archives of Environmental Contamination and Toxicology, 2020)

Structural genomic variation leads to genetic differentiation in Lake Tanganyika's sardines - Julian Junker; Jessica A. Rick; Peter B. McIntyre; Ismael Kimirei; Emmanuel A. Sweke; Julieth B. Mosille; Bernhard Wehrli; Christian Dinkel; Salome Mwaiko; Ole Seehausen; Catherine E. Wagner (Molecular Ecology, 2020)
Identifying patterns in genetic structure and the genetic basis of ecological adaptation is a core goal of evolutionary biology and can inform the management and conservation of species that are vulnerable to population declines exacerbated by climate change. We used reduced‐representation genomic sequencing methods to gain a better understanding of genetic structure among and within populations of Lake Tanganyika's two sardine species, Limnothrissa miodon and Stolothrissa tanganicae . Samples of these ecologically and economically important species were collected across the length of Lake Tanganyika, as well as from nearby Lake Kivu, where L. miodon was introduced in 1959. Our results reveal differentiation within both S. tanganicae and L. miodon that is not explained by geography. Instead, this genetic differentiation is due to the presence of large sex‐specific regions in the genomes of both species, but involving different polymorphic sites in each species. Our results therefore indicate rapidly evolving XY sex determination in the two species. Additionally, we found evidence of a large chromosomal rearrangement in L. miodon , creating two homokaryotypes and one heterokaryotype. We found all karyotypes throughout Lake Tanganyika, but the frequencies vary along a north–south gradient and differ substantially in the introduced Lake Kivu population. We do not find evidence for significant isolation by distance, even over the hundreds of kilometres covered by our sampling, but we do find shallow population structure.

Overcoming the Obstacles Faced by Early Career Researchers in Marine Science: Lessons From the Marine Ecosystem Assessment for the Southern Ocean - Madeleine J. Brasier; Stacey McCormack; Narissa Bax; Jilda A. Caccavo; Emma Cavan; Jessica A. Ericson; Blanca Figuerola; Alyce Hancock; Svenja Halfter; Nicole Hellessey; Juan Höfer; Peter S. Puskic; et al. (Frontiers in Marine Science, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Ecological and genomic analyses of candidate phylum WPS ‐2 bacteria in an unvegetated soil - Andriy Sheremet; Gareth M. Jones; Jessica Jarett; Robert M. Bowers; Isaac Bedard; Cassandra Culham; Emiley A. Eloe‐Fadrosh; Natalia Ivanova; Rex R. Malmstrom; Stephen E. Grasby; Tanja Woyke; Peter F. Dunfield (Environmental Microbiology, 2020)
Summary Members of the bacterial candidate phylum WPS‐2 (or Eremiobacterota) are abundant in several dry, bare soil environments. In a bare soil deposited by an extinct iron–sulfur spring, we found that WPS‐2 comprised up to 24% of the bacterial community and up to 10 8 cells per g of soil based on 16S rRNA gene sequencing and quantification. A single genus‐level cluster ( Ca. Rubrimentiphilum) predominated in bare soils but was less abundant in adjacent forest. Nearly complete genomes of Ca. Rubrimentiphilum were recovered as single amplified genomes (SAGs) and metagenome‐assembled genomes (MAGs). Surprisingly, given the abundance of WPS‐2 in bare soils, the genomes did not indicate any capacity for autotrophy, phototrophy, or trace gas metabolism. Instead, they suggest a predominantly aerobic organoheterotrophic lifestyle, perhaps based on scavenging amino acids, nucleotides, and complex oligopeptides, along with lithotrophic capacity on thiosulfate. Network analyses of the entire community showed that some species of Chloroflexi , Actinobacteria , and candidate phylum AD3 (or Dormibacterota) co‐occurred with Ca. Rubrimentiphilum and may represent ecological or metabolic partners. We propose that Ca. Rubrimentiphilum act as efficient heterotrophic scavengers. Combined with previous studies, these data suggest that the phylum WPS‐2 includes bacteria with diverse metabolic capabilities.

A First Global Oceanic Compilation of Observational Dissolved Aluminum Data With Regional Statistical Data Treatment - Jan-Lukas Menzel Barraqueta; Saumik Samanta; Eric P. Achterberg; Andrew R. Bowie; Peter Croot; Ryan Cloete; Tara De Jongh; Maria D. Gelado-Caballero; Jessica K. Klar; Rob Middag; Jean C. Loock; Tomas A. Remenyi; et al. (Frontiers in Marine Science, 2020)

Prioritizing river basins for intensive monitoring and assessment by the US Geological Survey - Peter C. Van Metre; Sharon Qi; Jeffrey Deacon; Cheryl Dieter; Jessica M. Driscoll; Michael Fienen; Terry Kenney; Patrick Lambert; David Lesmes; Christopher A. Mason; Anke Mueller-Solger; Marylynn Musgrove; et al. (Environmental Monitoring and Assessment, 2020)
The US Geological Survey (USGS) is currently (2020) integrating its water science programs to better address the nation’s greatest water resource challenges now and into the future. This integration will rely, in part, on data from 10 or more intensively monitored river basins from across the USA. A team of USGS scientists was convened to develop a systematic, quantitative approach to prioritize candidate basins for this monitoring investment to ensure that, as a group, the 10 basins will support the assessment and forecasting objectives of the major USGS water science programs. Candidate basins were the level-4 hydrologic units (HUC04) with some of the smaller HUC04s being combined; median candidate-basin area is 46,600 km 2 . Candidate basins for the contiguous United States (CONUS) were grouped into 18 hydrologic regions. Ten geospatial variables representing land use, climate change, water use, water-balance components, streamflow alteration, fire risk, and ecosystem sensitivity were selected to rank candidate basins within each of the 18 hydrologic regions. The two highest ranking candidate basins in each of the 18 regions were identified as finalists for selection as “Integrated Water Science Basins”; final selection will consider input from a variety of stakeholders. The regional framework, with only one basin selected per region, ensures that as a group, the basins represent the range in major drivers of the hydrologic cycle. Ranking within each region, primarily based on anthropogenic stressors of water resources, ensures that settings representing important water-resource challenges for the nation will be studied.

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

Stokes drift of plankton in linear internal waves: Cross‐shore transport of neutrally buoyant and depth‐keeping organisms - Peter J. S. Franks; Jessica C. Garwood; Michael Ouimet; Jorge Cortes; Ruth C. Musgrave; Andrew J. Lucas (Limnology and Oceanography, 2020)
The meroplanktonic larvae of many invertebrate and vertebrate species rely on physical transport to move them across the shelf to their adult habitats. One potential mechanism for cross‐shore larval transport is Stokes drift in internal waves. Here, we develop theory to quantify the Stokes velocities of neutrally buoyant and depth‐keeping organisms in linear internal waves in shallow water. We apply the analyses to theoretical and measured internal wave fields, and compare results with a numerical model. Near the surface and bottom boundaries, both neutrally buoyant and depth‐keeping organisms were transported in the direction of the wave's phase propagation. However, neutrally buoyant organisms were transported in the opposite direction of the wave's phase at mid depths, while depth‐keeping organisms had zero net transport there. Weakly depth‐keeping organisms had Stokes drifts between the perfectly depth‐keeping and neutrally buoyant organisms. For reasonable wave amplitudes and phase speeds, organisms would experience horizontal Stokes speeds of several centimeters per second—or a few kilometers per day in a constant wave field. With onshore‐polarized internal waves, Stokes drift in internal waves presents a predictable mechanism for onshore transport of meroplanktonic larvae and other organisms near the surface, and offshore transport at mid depths.

The Bacterial Microbiome of the Long-Term Aquarium Cultured High-Microbial Abundance Sponge Haliclona cnidata – Sustained Bioactivity Despite Community Shifts Under Detrimental Conditions - Johannes Schellenberg; Jessica Reichert; Martin Hardt; Ines Klingelhöfer; Gertrud Morlock; Patrick Schubert; Mina Bižić; Hans-Peter Grossart; Peter Kämpfer; Thomas Wilke; Stefanie P. Glaeser (Frontiers in Marine Science, 2020)

Creation and characterization of an immortalized canine myoblast cell line: Myok9 - Sara Mata López; Cynthia Balog-Alvarez; Emily H. Canessa; Yetrib Hathout; Kristy J. Brown; Stanislav Vitha; Amanda K. Bettis; Jessica Boehler; Joe N. Kornegay; Peter P. Nghiem (Mammalian Genome, 2020)

Behavioral Responses of Sea Lamprey to Varying Application Rates of a Synthesized Pheromone in Diverse Trapping Scenarios - Nicholas S. Johnson; Sean A. Lewandoski; Bethany J. Alger; Lisa O’Connor; Gale Bravener; Peter Hrodey; Belinda Huerta; Jessica Barber; Weiming Li; C. Michael Wagner; Michael J. Siefkes (Journal of Chemical Ecology, 2020)

Nitrogen assimilation in picocyanobacteria inhabiting the oxygen‐deficient waters of the eastern tropical North and South Pacific - Montserrat Aldunate; Carlos Henríquez‐Castillo; Qixing Ji; Jessica Lueders‐Dumont; Margaret R. Mulholland; Bess B. Ward; Peter von Dassow; Osvaldo Ulloa (Limnology and Oceanography, 2020)
Prochlorococcus and Synechococcus are the most abundant free‐living photosynthetic microorganisms in the ocean. Uncultivated lineages of these picocyanobacteria also thrive in the dimly illuminated upper part of oxygen‐deficient zones (ODZs), where an important portion of ocean nitrogen (N) loss takes place via denitrification and anaerobic ammonium oxidation. Recent metagenomic studies revealed that ODZ Prochlorococcus have the genetic potential for using different N forms, including nitrate and nitrite, uncommon N sources for Prochlorococcus , but common for Synechococcus . To determine which N sources ODZ picocyanobacteria are actually using in nature, the cellular 15 N natural abundance (δ 15 N) and assimilation rates of different N compounds were determined using cell sorting by flow cytometry and mass spectrometry. The natural δ 15 N of the ODZ Prochlorococcus varied from −4.0‰ to 13.0‰ ( n = 9), with 50% of the values in the range of −2.1–2.6‰. While the highest values suggest nitrate use, most observations indicate the use of nitrite, ammonium, or a mixture of N sources. Meanwhile, incubation experiments revealed potential assimilation rates of ammonium and urea in the same order of magnitude as that expected for total N in several environments including ODZs, whereas rates of nitrite and nitrate assimilation were very low. Our results thus indicate that reduced forms of N and nitrite are the dominant sources for ODZ picocyanobacteria, although nitrate might be important on some occasions. ODZ picocyanobacteria might thus represent potential competitors with anammox bacteria for ammonium and nitrite, with ammonia‐oxidizing archaea for ammonium, and with nitrite‐oxidizing bacteria for nitrite.

New insights into the seasonal diet of Antarctic krill using triacylglycerol and phospholipid fatty acids, and sterol composition - Jessica A. Ericson; Nicole Hellessey; Peter D. Nichols; Stephen Nicol; So Kawaguchi; Nils Hoem; Patti Virtue (Polar Biology, 2019)

Reducing negative affect with anodal transcranial direct current stimulation increases memory performance in young—but not in elderly—individuals - Jessica Peter; Elisabeth Neumann-Dunayevska; Franziska Geugelin; Nadia Ninosu; Christian Plewnia; Stefan Klöppel (Brain Structure and Function, 2019)

A resting state fMRI analysis pipeline for pooling inference across diverse cohorts: an ENIGMA rs-fMRI protocol - Bhim M. Adhikari; Neda Jahanshad; Dinesh Shukla; Jessica Turner; Dominik Grotegerd; Udo Dannlowski; Harald Kugel; Jennifer Engelen; Bruno Dietsche; Axel Krug; Tilo Kircher; Els Fieremans; et al. (Brain Imaging and Behavior, 2019)

Response of cyanobacteria and phytoplankton abundance to warming, extreme rainfall events and nutrient enrichment - Jessica Richardson; Heidrun Feuchtmayr; Claire Miller; Peter D. Hunter; Stephen C. Maberly; Laurence Carvalho (Global Change Biology, 2019)
Cyanobacterial blooms are an increasing threat to water quality and global water security caused by the nutrient enrichment of freshwaters. There is also a broad consensus that blooms are increasing with global warming, but the impacts of other concomitant environmental changes, such as an increase in extreme rainfall events, may affect this response. One of the potential effects of high rainfall events on phytoplankton communities is greater loss of biomass through hydraulic flushing. Here we used a shallow lake mesocosm experiment to test the combined effects of: warming (ambient vs. +4°C increase), high rainfall (flushing) events (no events vs. seasonal events) and nutrient loading (eutrophic vs. hypertrophic) on total phytoplankton chlorophyll‐ a and cyanobacterial abundance and composition. Our hypotheses were that: (a) total phytoplankton and cyanobacterial abundance would be higher in heated mesocosms; (b) the stimulatory effects of warming on cyanobacterial abundance would be enhanced in higher nutrient mesocosms, resulting in a synergistic interaction; (c) the recovery of biomass from flushing induced losses would be quicker in heated and nutrient‐enriched treatments, and during the growing season. The results supported the first and, in part, the third hypotheses: total phytoplankton and cyanobacterial abundance increased in heated mesocosms with an increase in common bloom‐forming taxa— Microcystis spp. and Dolichospermum spp. Recovery from flushing was slowest in the winter, but unaffected by warming or higher nutrient loading. Contrary to the second hypothesis, an antagonistic interaction between warming and nutrient enrichment was detected for both cyanobacteria and chlorophyll‐ a demonstrating that ecological surprises can occur, dependent on the environmental context. While this study highlights the clear need to mitigate against global warming, oversimplification of global change effects on cyanobacteria should be avoided; stressor gradients and seasonal effects should be considered as important factors shaping the response.

Presence of a basic secretory protein in xylem sap and shoots of poplar in winter and its physicochemical activities against winter environmental conditions - Tsutomu Aohara; Jun Furukawa; Kenji Miura; Sakae Tsuda; Jessica S. Poisson; Robert N. Ben; Peter W. Wilson; Shinobu Satoh (Journal of Plant Research, 2019)

Ocean FAIR Data Services - Toste Tanhua; Sylvie Pouliquen; Jessica Hausman; Kevin O’Brien; Pip Bricher; Taco de Bruin; Justin J. H. Buck; Eugene F. Burger; Thierry Carval; Kenneth S. Casey; Steve Diggs; Alessandra Giorgetti; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

What is marine justice? - Jennifer A. Martin; Summer Gray; Eréndira Aceves-Bueno; Peter Alagona; Tammy L. Elwell; Angela Garcia; Zach Horton; David Lopez-Carr; Jessica Marter-Kenyon; Karly Marie Miller; Christopher Severen; Teresa Shewry; et al. (Journal of Environmental Studies and Sciences, 2019)

Conventional land‐use intensification reduces species richness and increases production: A global meta‐analysis - Michael Beckmann; Katharina Gerstner; Morodoluwa Akin‐Fajiye; Silvia Ceaușu; Stephan Kambach; Nicole L. Kinlock; Helen R. P. Phillips; Willem Verhagen; Jessica Gurevitch; Stefan Klotz; Tim Newbold; Peter H. Verburg; et al. (Global Change Biology, 2019)
Most current research on land‐use intensification addresses its potential to either threaten biodiversity or to boost agricultural production. However, little is known about the simultaneous effects of intensification on biodiversity and yield. To determine the responses of species richness and yield to conventional intensification, we conducted a global meta‐analysis synthesizing 115 studies which collected data for both variables at the same locations. We extracted 449 cases that cover a variety of areas used for agricultural (crops, fodder) and silvicultural (wood) production. We found that, across all production systems and species groups, conventional intensification is successful in increasing yield (grand mean + 20.3%), but it also results in a loss of species richness (−8.9%). However, analysis of sub‐groups revealed inconsistent results. For example, small intensification steps within low intensity systems did not affect yield or species richness. Within high‐intensity systems species losses were non‐significant but yield gains were substantial (+15.2%). Conventional intensification within medium intensity systems revealed the highest yield increase (+84.9%) and showed the largest loss in species richness (−22.9%). Production systems differed in their magnitude of richness response, with insignificant changes in silvicultural systems and substantial losses in crop systems (−21.2%). In addition, this meta‐analysis identifies a lack of studies that collect robust biodiversity (i.e. beyond species richness) and yield data at the same sites and that provide quantitative information on land‐use intensity. Our findings suggest that, in many cases, conventional land‐use intensification drives a trade‐off between species richness and production. However, species richness losses were often not significantly different from zero, suggesting even conventional intensification can result in yield increases without coming at the expense of biodiversity loss. These results should guide future research to close existing research gaps and to understand the circumstances required to achieve such win‐win or win‐no‐harm situations in conventional agriculture.

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

How commercial fishing effort is managed - Christopher M. Anderson; Melissa J. Krigbaum; Martin C. Arostegui; Megan L. Feddern; John Zachary Koehn; Peter T. Kuriyama; Christina Morrisett; Caitlin I. Allen Akselrud; Melanie J. Davis; Courtney Fiamengo; Ava Fuller; Qi Lee; et al. (Fish and Fisheries, 2019)
Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world ( http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.

The Precursor Hypothesis of Sponge Kleptocnidism: Development of Nematocysts in Haliclona cnidata sp. nov. (Porifera, Demospongiae, Haplosclerida) - Johannes Schellenberg; Jessica Reichert; Martin Hardt; Henrike Schmidtberg; Peter Kämpfer; Stefanie P. Glaeser; Patrick Schubert; Thomas Wilke (Frontiers in Marine Science, 2019)

Potential for offsetting diamond mine carbon emissions through mineral carbonation of processed kimberlite: an assessment of De Beers mine sites in South Africa and Canada - Evelyn M. Mervine; Sasha Wilson; Ian M. Power; Gregory M. Dipple; Connor C. Turvey; Jessica L. Hamilton; Sterling Vanderzee; Mati Raudsepp; Colette Southam; Juerg M. Matter; Peter B. Kelemen; Johann Stiefenhofer; et al. (Mineralogy and Petrology, 2018)

Hydrologic monitoring tools for freshwater municipal planning in the Arctic: the case of Iqaluit, Nunavut, Canada - Michael Bakaic; Andrew Scott Medeiros; Jessica F. Peters; Brent B. Wolfe (Environmental Science and Pollution Research, 2018)

Effects of multiple stressors on cyanobacteria abundance vary with lake type - Jessica Richardson; Claire Miller; Stephen C. Maberly; Philip Taylor; Lidija Globevnik; Peter Hunter; Erik Jeppesen; Ute Mischke; S. Jannicke Moe; Agnieszka Pasztaleniec; Martin Søndergaard; Laurence Carvalho (Global Change Biology, 2018)
Blooms of cyanobacteria are a current threat to global water security that is expected to increase in the future because of increasing nutrient enrichment, increasing temperature and extreme precipitation in combination with prolonged drought. However, the responses to multiple stressors, such as those above, are often complex and there is contradictory evidence as to how they may interact. Here we used broad scale data from 494 lakes in central and northern Europe, to assess how cyanobacteria respond to nutrients (phosphorus), temperature and water retention time in different types of lakes. Eight lake types were examined based on factorial combinations of major factors that determine phytoplankton composition and sensitivity to nutrients: alkalinity (low and medium‐high), colour (clear and humic) and mixing intensity (polymictic and stratified). In line with expectations, cyanobacteria increased with temperature and retention time in five of the eight lake types. Temperature effects were greatest in lake types situated at higher latitudes, suggesting that lakes currently not at risk could be affected by warming in the future. However, the sensitivity of cyanobacteria to temperature, retention time and phosphorus varied among lake types highlighting the complex responses of lakes to multiple stressors. For example, in polymictic, medium‐high alkalinity, humic lakes cyanobacteria biovolume was positively explained by retention time and a synergy between TP and temperature, while in polymictic, medium‐high alkalinity, clear lakes only retention time was identified as an explanatory variable. These results show that, although climate change will need to be accounted for when managing the risk of cyanobacteria in lakes, a “one‐size fits‐all” approach is not appropriate. When forecasting the response of cyanobacteria to future environmental change, including changes caused by climate and local management, it will be important to take this differential sensitivity of lakes into account.

Critical Information Gaps Impeding Understanding of the Role of Larval Connectivity Among Coral Reef Islands in an Era of Global Change - Peter J. Edmunds; Shelby E. McIlroy; Mehdi Adjeroud; Put Ang; Jessica L. Bergman; Robert C. Carpenter; Mary A. Coffroth; Atsushi G. Fujimura; James L. Hench; Sally J. Holbrook; James J. Leichter; Soyoka Muko; et al. (Frontiers in Marine Science, 2018)

Serum cytokine responses in Rickettsia felis infected febrile children, Ghana - Jessica Rauch; Peter Sothmann; Cassandra Aldrich; Ben Hogan; Ellis Owusu-Dabo; Jürgen May; Daniel Eibach; Dennis Tappe (Medical Microbiology and Immunology, 2018)

Metabolic potential and in situ transcriptomic profiles of previously uncharacterized key microbial groups involved in coupled carbon, nitrogen and sulfur cycling in anoxic marine zones - Alvaro M. Plominsky; Nicole Trefault; Sheila Podell; Jessica M. Blanton; Rodrigo De la Iglesia; Eric E. Allen; Peter von Dassow; Osvaldo Ulloa (Environmental Microbiology, 2018)
Summary Anoxic marine zones (AMZs) impact biogeochemical cycles at the global scale, particularly the nitrogen cycle. Key microbial players from AMZs have been identified, but the majority remains unrecognized or uncharacterized. Thirty‐one single‐cell amplified genomes (SAGs) from the eastern tropical North and South Pacific AMZs were sequenced to gain insight into the distribution, metabolic potential and contribution to the community transcriptional profile of these uncharacterized bacterial and archaeal groups. Detailed analyses focused on SAG‐bins assigned to three of these groups that presented 79%–100% estimated genome completeness: the putative sulphur‐oxidizing Gamaproteobacteria EOSA II clade, a Marinimicrobia member of the recently recognized PN262000N21 clade found to be abundant in AMZ anoxic cores, and a representative of the Marine Benthic Group A Thaumarchaeota. Community‐based analyses revealed that these three groups are significantly more abundant and transcriptionally more active in the AMZ microbial communities than previously described phylogenetically related microbial groups. Collectively, these groups have the potential to link biogeochemically relevant processes by coupling the carbon, nitrogen and sulfur cycles. Together, these results increase our understanding of key microbial components inhabiting AMZs and other oxygen‐deficient marine environments, enhancing our capacity to predict the impact of the expansion of these ecosystems due to climate change.

Working (longer than) 9 to 5: are there cardiometabolic health risks for young Australian workers who report longer than 38-h working weeks? - Amy C. Reynolds; Romola S. Bucks; Jessica L. Paterson; Sally A. Ferguson; Trevor A. Mori; Nigel McArdle; Leon Straker; Lawrence J. Beilin; Peter R. Eastwood (International Archives of Occupational and Environmental Health, 2018)

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

Enabling global exchange of groundwater data: GroundWaterML2 (GWML2) - Boyan Brodaric; Eric Boisvert; Laurence Chery; Peter Dahlhaus; Sylvain Grellet; Alexander Kmoch; François Létourneau; Jessica Lucido; Bruce Simons; Bernhard Wagner (Hydrogeology Journal, 2018)

A boundary current drives synchronous growth of marine fishes across tropical and temperate latitudes - Joyce J. L. Ong; Adam N. Rountrey; Bryan A. Black; Hoang Minh Nguyen; Peter G. Coulson; Stephen J. Newman; Corey B. Wakefield; Jessica J. Meeuwig; Mark G. Meekan (Global Change Biology, 2018)
Entrainment of growth patterns of multiple species to single climatic drivers can lower ecosystem resilience and increase the risk of species extinction during stressful climatic events. However, predictions of the effects of climate change on the productivity and dynamics of marine fishes are hampered by a lack of historical data on growth patterns. We use otolith biochronologies to show that the strength of a boundary current, modulated by the El Niño‐Southern Oscillation, accounted for almost half of the shared variance in annual growth patterns of five of six species of tropical and temperate marine fishes across 23° of latitude (3000 km) in Western Australia. Stronger flow during La Niña years drove increased growth of five species, whereas weaker flow during El Niño years reduced growth. Our work is the first to link the growth patterns of multiple fishes with a single oceanographic/climate phenomenon at large spatial scales and across multiple climate zones, habitat types, trophic levels and depth ranges. Extreme La Niña and El Niño events are predicted to occur more frequently in the future and these are likely to have implications for these vulnerable ecosystems, such as a limited capacity of the marine taxa to recover from stressful climatic events.

Behavior of Brooded Coral Larvae in Response to Elevated pCO2 - Jessica L. Bergman; Saki Harii; Haruko Kurihara; Peter J. Edmunds (Frontiers in Marine Science, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Organic Agriculture 3.0 is innovation with research - Gerold Rahmann; M. Reza Ardakani; Paolo Bàrberi; Herwart Boehm; Stefano Canali; Mahesh Chander; Wahyudi David; Lucas Dengel; Jan Willem Erisman; Ana C. Galvis-Martinez; Ulrich Hamm; Johannes Kahl; et al. (Organic Agriculture, 2017)

Erratum to: Perseveration in a spatial-discrimination serial reversal learning task is differentially affected by MAO-A and MAO-B inhibition and associated with reduced anxiety and peripheral serotonin levels - Peter Zhukovsky; Johan Alsiö; Bianca Jupp; Jing Xia; Chiara Giuliano; Lucy Jenner; Jessica Griffiths; Errin Riley; Sajeed Ali; Angela C. Roberts; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2017)

A genetic risk score is differentially associated with migraine with and without aura - Claudia Pisanu; Martin Preisig; Enrique Castelao; Jennifer Glaus; Giorgio Pistis; Alessio Squassina; Maria Del Zompo; Kathleen R. Merikangas; Gérard Waeber; Peter Vollenweider; Jessica Mwinyi; Helgi B. Schiöth (Human Genetics, 2017)

Perseveration in a spatial-discrimination serial reversal learning task is differentially affected by MAO-A and MAO-B inhibition and associated with reduced anxiety and peripheral serotonin levels - Peter Zhukovsky; Johan Alsiö; Bianca Jupp; Jing Xia; Chiara Guiliano; Lucy Jenner; Jessica Griffiths; Errin Riley; Sajeed Ali; Angela C. Roberts; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2017)

Water security for northern peoples: review of threats to Arctic freshwater systems in Nunavut, Canada - Andrew S. Medeiros; Patricia Wood; Sonia D. Wesche; Michael Bakaic; Jessica F. Peters (Regional Environmental Change, 2017)

Insights into Blainville's beaked whale ( Mesoplodon densirostris ) echolocation ontogeny from recordings of mother‐calf pairs - Charlotte Dunn; Diane Claridge; John Durban; Jessica Shaffer; David Moretti; Peter Tyack; Luke Rendell (Marine Mammal Science, 2017)

Contact rates of wild-living and domestic dog populations in Australia: a new approach - Jessica Sparkes; Guy Ballard; Peter J. S. Fleming; Remy van de Ven; Gerhard Körtner (Oecologia, 2016)

Teletoxicology: Patient Assessment Using Wearable Audiovisual Streaming Technology - Aaron B. Skolnik; Peter R. Chai; Christian Dameff; Richard Gerkin; Jessica Monas; Angela Padilla-Jones; Steven Curry (Journal of Medical Toxicology, 2016)

Taxonomic distinctness in the diet of two sympatric marine turtle species - Thomas B. Stringell; Wesley V. Clerveaux; Brendan J. Godley; Flora E. A. Kent; Emma D. G. Lewis; Jessica E. Marsh; Quinton Phillips; Peter B. Richardson; Amdeep Sanghera; Annette C. Broderick (Marine Ecology, 2016)
Marine turtles are considered keystone consumers in tropical coastal ecosystems and their decline through overexploitation has been implicated in the deterioration of reefs and seagrass pastures in the Caribbean. In the present study, we analysed stomach contents of green ( Chelonia mydas ) and hawksbill turtles ( Eretmochelys imbricata ) harvested in the legal turtle fishery of the Turks and Caicos Islands (Caribbean) during 2008–2010. Small juveniles to adult‐sized turtles were sampled. Together with data from habitat surveys, we assessed diet composition and the taxonomic distinctness (and other species diversity measures) in the diets of these sympatric marine turtle species. The diet of green turtles (n = 92) consisted of a total of 47 taxa: including three species of seagrass (present in 99% of individuals), 29 species of algae and eight sponge species. Hawksbill turtles (n = 45) consumed 73 taxa and were largely spongivorous (16 species; sponges present in 100% of individuals) but also foraged on 50 species of algae (present in 73% of individuals) and three species of seagrass. Plastics were found in trace amounts in 4% of green turtle and 9% of hawksbill turtle stomach samples. We expected to find changes in diet that might reflect ontogenetic shifts from small (oceanic‐pelagic) turtles to larger (coastal‐benthic) turtles. Dietary composition (abundance and biomass), however, did not change significantly with turtle size, although average taxonomic distinctness was lower in larger green turtles. There was little overlap in prey between the two turtle species, suggesting niche separation. Taxonomic distinctness routines indicated that green turtles had the most selective diet, whereas hawksbill turtles were less selective than expected when compared with the relative frequency and biomass of diet items. We discuss these findings in relation to the likely important trophic roles that these sympatric turtle species play in reef and seagrass habitats.

Adaptation in isolated populations: when does it happen and when can we tell? - Jessica L. Crisci; Matthew D. Dean; Peter Ralph (Molecular Ecology, 2016)
Isolated populations with novel phenotypes present an exciting opportunity to uncover the genetic basis of ecologically significant adaptation, and genomic scans have often, but not always, led to candidate genes directly related to an adaptive phenotype. However, in many cases these populations were established by a severe bottleneck, which can make identifying targets of selection problematic. Here, we simulate severe bottlenecks and subsequent selection on standing variation, mimicking adaptation after establishment of a new small population, such as an island or an artificial selection experiment. Using simulations of single loci under positive selection and population genetics theory, we examine how population size and age of the population isolate affect the ability of outlier scans for selection to identify adaptive alleles using both single‐site measures and haplotype structure. We find and explain an optimal combination of selection strength, starting frequency, and age of the adaptive allele, which we refer to as a Goldilocks zone, where adaptation is likely to occur and yet the adaptive variants are most likely to derive from a single ancestor (a ‘hard’ selective sweep); in this zone, four commonly used statistics detect selection with high power. Real‐world examples of both island colonization and experimental evolution studies are discussed. Our study provides concrete considerations to be made before embarking on whole‐genome sequencing of differentiated populations.

Controlling range expansion in habitat networks by adaptively targeting source populations - Karlo Hock; Nicholas H. Wolff; Roger Beeden; Jessica Hoey; Scott A. Condie; Kenneth R. N. Anthony; Hugh P. Possingham; Peter J. Mumby (Conservation Biology, 2016)
Controlling the spread of invasive species, pests, and pathogens is often logistically limited to interventions that target specific locations at specific periods. However, in complex, highly connected systems, such as marine environments connected by ocean currents, populations spread dynamically in both space and time via transient connectivity links. This results in nondeterministic future distributions of species in which local populations emerge dynamically and concurrently over a large area. The challenge, therefore, is to choose intervention locations that will maximize the effectiveness of the control efforts. We propose a novel method to manage dynamic species invasions and outbreaks that identifies the intervention locations most likely to curtail population expansion by selectively targeting local populations most likely to expand their future range. Critically, at any point during the development of the invasion or outbreak, the method identifies the local intervention that maximizes the long‐term benefit across the ecosystem by restricting species’ potential to spread. In so doing, the method adaptively selects the intervention targets under dynamically changing circumstances. To illustrate the effectiveness of the method we applied it to controlling the spread of crown‐of‐thorns starfish ( Acanthaster sp.) outbreaks across Australia's Great Barrier Reef. Application of our method resulted in an 18‐fold relative improvement in management outcomes compared with a random targeting of reefs in putative starfish control scenarios. Although we focused on applying the method to reducing the spread of an unwanted species, it can also be used to facilitate the spread of desirable species through connectivity networks. For example, the method could be used to select those fragments of habitat most likely to rebuild a population if they were sufficiently well protected.

Moss stable isotopes (carbon-13, oxygen-18) and testate amoebae reflect environmental inputs and microclimate along a latitudinal gradient on the Antarctic Peninsula - Jessica Royles; Matthew J. Amesbury; Thomas P. Roland; Glyn D. Jones; Peter Convey; Howard Griffiths; Dominic A. Hodgson; Dan J. Charman (Oecologia, 2016)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Hydrological Change in the Coorong Estuary, Australia, Past and Present: Evidence from Fossil Invertebrate and Algal Assemblages - Jessica M. Reeves; Deborah Haynes; Adriana García; Peter A. Gell (Estuaries and Coasts, 2015)

Differences in genetic variation in antigen-processing machinery components and association with cervical carcinoma risk in two Indonesian populations - Akash M. Mehta; Vivian M. Spaans; Nyoman Bayu Mahendra; Elisabeth M. Osse; Jessica N. I. Vet; Gatot Purwoto; I. G. D. Surya; Santoso Cornian; Alexander A. Peters; Gert J. Fleuren; Ekaterina S. Jordanova (Immunogenetics, 2015)

Long‐term declines in nutritional quality of tropical leaves - Jessica M. Rothman; Colin A. Chapman; Thomas T. Struhsaker; David Raubenheimer; Dennis Twinomugisha; Peter G. Waterman (Ecology, 2015)
Global change is affecting plant and animal populations and many of the changes are likely subtle and difficult to detect. Based on greenhouse experiments, changes in temperature and rainfall, along with elevated CO 2 , are expected to impact the nutritional quality of leaves. Here, we show a decline in the quality of tree leaves 15 and 30 years after two previous studies in an undisturbed area of tropical forest in Kibale National Park, Uganda. After 30 years in a sample of multiple individuals of ten tree species, the mature leaves of all but one species increased in fiber concentrations, with a mean increase of 10%; tagged individuals of one species increased 13% in fiber. After 15 years, in eight tree species the fiber of young leaves increased 15%, and protein decreased 6%. Like many folivores, Kibale colobus monkeys select leaves with a high protein‐to‐fiber ratio, so for these folivores declining leaf quality could have a major impact. Comparisons among African and Asian forests show a strong correlation between colobine biomass and the protein‐to‐fiber ratio of the mature leaves from common tree species. Although this model, predicts a 31% decline in monkey abundance for Kibale, we have not yet seen these declines.

Internal models of upper limb prosthesis users when grasping and lifting a fragile object with their prosthetic limb - Peter S. Lum; Iian Black; Rahsaan J. Holley; Jessica Barth; Alexander W. Dromerick (Experimental Brain Research, 2014)

Hypothesis-independent pathway analysis implicates GABA and Acetyl-CoA metabolism in primary open-angle glaucoma and normal-pressure glaucoma - Jessica N. Cooke Bailey; Brian L. Yaspan; Louis R. Pasquale; Michael A. Hauser; Jae H. Kang; Stephanie J. Loomis; Murray Brilliant; Donald L. Budenz; William G. Christen; John Fingert; Douglas Gaasterland; Terry Gaasterland; et al. (Human Genetics, 2014)

Towards a phylogenetic classification of reef corals: the I ndo‐ P acific genera M erulina , G oniastrea and S capophyllia ( S cleractinia, M erulinidae) - Danwei Huang; Francesca Benzoni; Roberto Arrigoni; Andrew H. Baird; Michael L. Berumen; Jessica Bouwmeester; Loke Ming Chou; Hironobu Fukami; Wilfredo Y. Licuanan; Edward R. Lovell; Rudolf Meier; Peter A. Todd; et al. (Zoologica Scripta, 2014)
Recent advances in scleractinian systematics and taxonomy have been achieved through the integration of molecular and morphological data, as well as rigorous analysis using phylogenetic methods. In this study, we continue in our pursuit of a phylogenetic classification by examining the evolutionary relationships between the closely related reef coral genera M erulina , G oniastrea , P araclavarina and S capophyllia (Merulinidae). In particular, we address the extreme polyphyly of F avites and G oniastrea that was discovered a decade ago. We sampled 145 specimens belonging to 16 species from a wide geographic range in the I ndo‐ P acific, focusing especially on type localities, including the Red Sea, western Indian Ocean and central Pacific. Tree reconstructions based on both nuclear and mitochondrial markers reveal a novel lineage composed of three species previously placed in F avites and G oniastrea . Morphological analyses indicate that this clade, P aragoniastrea H uang, B enzoni & B udd, gen. n., has a unique combination of corallite and subcorallite features observable with scanning electron microscopy and thin sections. Molecular and morphological evidence furthermore indicates that the monotypic genus Paraclavarina is nested within Merulina , and the former is therefore synonymised.

Water temperature and fish growth: otoliths predict growth patterns of a marine fish in a changing climate - Adam N. Rountrey; Peter G. Coulson; Jessica J. Meeuwig; Mark Meekan (Global Change Biology, 2014)
Ecological modeling shows that even small, gradual changes in body size in a fish population can have large effects on natural mortality, biomass, and catch. However, efforts to model the impact of climate change on fish growth have been hampered by a lack of long‐term (multidecadal) data needed to understand the effects of temperature on growth rates in natural environments. We used a combination of dendrochronology techniques and additive mixed‐effects modeling to examine the sensitivity of growth in a long‐lived (up to 70 years), endemic marine fish, the western blue groper ( Achoerodus gouldii ), to changes in water temperature. A multi‐decadal biochronology (1952–2003) of growth was constructed from the otoliths of 56 fish collected off the southwestern coast of Western Australia, and we tested for correlations between the mean index chronology and a range of potential environmental drivers. The chronology was significantly correlated with sea surface temperature in the region, but common variance among individuals was low. This suggests that this species has been relatively insensitive to past variations in climate. Growth increment and age data were also used in an additive mixed model to predict otolith growth and body size later this century. Although growth was relatively insensitive to changes in temperature, the model results suggested that a fish aged 20 in 2099 would have an otolith about 10% larger and a body size about 5% larger than a fish aged 20 in 1977. Our study shows that species or populations regarded as relatively insensitive to climate change could still undergo significant changes in growth rate and body size that are likely to have important effects on the productivity and yield of fisheries.

The secondary origin of diamonds: multi-modal radiation tomography of diamondiferous mantle eclogites - Geoffrey H. Howarth; Nikolay V. Sobolev; John F. Pernet-Fisher; Peter H. Barry; Dayakar Penumadu; Stephen Puplampu; Richard A. Ketcham; Jessica A. Maisano; Dawn Taylor; Lawrence A. Taylor (International Geology Review, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Cascadia Initiative: A Sea Change In Seismological Studies of Subduction Zones - Douglas Toomey; Richard Allen; Andrew Barclay; Samuel Bell; Peter Bromirski; Richard Carlson; Xiaowei Chen; John Collins; Robert Dziak; Brent Evers; Donald Forsyth; Peter Gerstoft; et al. (Oceanography, 2014)

Development of nineteen polymorphic microsatellite loci in the threatened polar bear (Ursus maritimus) using next generation sequencing - Jessica R. Brandt; Peter J. Van Coeverden de Groot; Kai Zhao; Markus G. Dyck; Peter T. Boag; Alfred L. Roca (Conservation Genetics Resources, 2014)

Prostate cancer derived prostatic acid phosphatase promotes an osteoblastic response in the bone microenvironment - Sandy R. Larson; Jessica Chin; Xiaotun Zhang; Lisha G. Brown; Ilsa M. Coleman; Bryce Lakely; Martin Tenniswood; Eva Corey; Peter S. Nelson; Robert L. Vessella; Colm Morrissey (Clinical & Experimental Metastasis, 2014)

No inflammatory gene-expression response to acute exercise in human Achilles tendinopathy - Jessica Pingel; Ulrich Fredberg; Lone Ramer Mikkelsen; Peter Schjerling; Katja Maria Heinemeier; Michael Kjaer; Adrian Harisson; Henning Langberg (European Journal of Applied Physiology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Faster but not smarter: effects of caffeine and caffeine withdrawal on alertness and performance - Peter J. Rogers; Susan V. Heatherley; Emma L. Mullings; Jessica E. Smith (Psychopharmacology, 2013)

Livestock greenhouse gas emissions and mitigation potential in Europe - Jessica Bellarby; Reyes Tirado; Adrian Leip; Franz Weiss; Jan Peter Lesschen; Pete Smith (Global Change Biology, 2013)
The livestock sector contributes considerably to global greenhouse gas emissions ( GHG ). Here, for the year 2007 we examined GHG emissions in the EU 27 livestock sector and estimated GHG emissions from production and consumption of livestock products; including imports, exports and wastage. We also reviewed available mitigation options and estimated their potential. The focus of this review is on the beef and dairy sector since these contribute 60% of all livestock production emissions. Particular attention is paid to the role of land use and land use change ( LULUC ) and carbon sequestration in grasslands. GHG emissions of all livestock products amount to between 630 and 863 Mt CO 2 e, or 12–17% of total EU 27 GHG emissions in 2007. The highest emissions aside from production, originate from LULUC , followed by emissions from wasted food. The total GHG mitigation potential from the livestock sector in Europe is between 101 and 377 Mt CO 2 e equivalent to between 12 and 61% of total EU 27 livestock sector emissions in 2007. A reduction in food waste and consumption of livestock products linked with reduced production, are the most effective mitigation options, and if encouraged, would also deliver environmental and human health benefits. Production of beef and dairy on grassland, as opposed to intensive grain fed production, can be associated with a reduction in GHG emissions depending on actual LULUC emissions. This could be promoted on rough grazing land where appropriate.

Hierarchical structure of juvenile hybrid aspen xylem revealed using X-ray scattering and microtomography - Kirsi Svedström; Jessica Lucenius; Jan Van den Bulcke; Denis Van Loo; Peter Immerzeel; Jussi-Petteri Suuronen; Loes Brabant; Joris Van Acker; Pekka Saranpää; Kurt Fagerstedt; Ewa Mellerowicz; Ritva Serimaa (Trees, 2012)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

Passive acoustic density estimation of sperm whales in the Tongue of the Ocean, Bahamas - Jessica A. W ard; Len Thomas; Susan Jarvis; Nancy DiMarzio; David Moretti; Tiago A. Marques; Charlotte Dunn; Diane C laridge; Eva Hartvig; Peter Tyack (Marine Mammal Science, 2012)
Long‐term passive acoustic monitoring of marine mammals on navy ranges provides the opportunity to better understand the potential impact of sonar on populations. The navy range in Tongue of the Ocean (TOTO), Bahamas contains extensive hydrophone arrays, potentially allowing estimation of the density of deep diving, vocally active species such as the sperm whale ( Physeter macrocephalus ). Previous visual surveys in TOTO have been of limited spatio–temporal coverage and resulted in only sporadic sightings of sperm whales, whereas passive acoustic observations suggest the species is present year round. However, until now the means of acoustically determining the specific number of individuals in each cluster has been limited. We used recently developed algorithms to identify the number of echolocating whales present during a 42 d study period. We screened a 297 h acoustic data set to determine the proportion of time animals were present; fifty 10 min samples during presence were analyzed to estimate the number of individuals vocalizing during each sample. These counts were combined with an independent estimate of the proportion of 10 min periods when tagged animals vocalize. The estimated average density was 0.16 whales/1,000 km 2 (CV 27%; 95% CI 0.095–0.264). The method is potentially applicable to other areas containing dense hydrophone arrays.

Carbon isotope evidence for recent climate‐related enhancement of CO 2 assimilation and peat accumulation rates in Antarctica - Jessica Royles; Jérôme Ogée; Lisa Wingate; Dominic A. Hodgson; Peter Convey; Howard Griffiths (Global Change Biology, 2012)
Signy Island, maritime Antarctic, lies within the region of the Southern Hemisphere that is currently experiencing the most rapid rates of environmental change. In this study, peat cores up to 2 m in depth from four moss banks on Signy Island were used to reconstruct changes in moss growth and climatic characteristics over the late Holocene. Measurements included radiocarbon dating (to determine peat accumulation rates) and stable carbon isotope composition of moss cellulose (to estimate photosynthetic limitation by CO 2 supply and model CO 2 assimilation rate). For at least one intensively 14 C‐dated Chorisodontium aciphyllum moss peat bank, the vertical accumulation rate of peat was 3.9 mm yr −1 over the last 30 years. Before the industrial revolution, rates of peat accumulation in all cores were much lower, at around 0.6–1 mm yr −1 . Carbon‐13 discrimination (Δ), corrected for background and anthropogenic source inputs, was used to develop a predictive model for CO 2 assimilation. Between 1680 and 1900, there had been a gradual increase in Δ, and hence assimilation rate. Since 1800, assimilation has also been stimulated by the changes in atmospheric CO 2 concentration, but a recent decline in Δ (over the past 50–100 years) can perhaps be attributed to documented changes in temperature and/or precipitation. The overall increase in CO 2 assimilation rate ( 13 C proxy) and enhanced C accumulation ( 14 C proxy) are consistent with warmer and wetter conditions currently generating higher growth rates than at any time in the past three millennia, with the decline in Δ perhaps compensated by a longer growing season.

Methods in Primate Nutritional Ecology: A User’s Guide - Jessica M. Rothman; Colin A. Chapman; Peter J. Van Soest (International Journal of Primatology, 2012)

Relationships Between Soil Microorganisms, Plant Communities, and Soil Characteristics in Chinese Subtropical Forests - Yu Ting Wu; Jessica Gutknecht; Karin Nadrowski; Christian Geißler; Peter Kühn; Thomas Scholten; Sabine Both; Alexandra Erfmeier; Martin Böhnke; Helge Bruelheide; Tesfaye Wubet; François Buscot (Ecosystems, 2012)

Invasion hotspots for non‐native plants in A ustralia under current and future climates - Jessica O'Donnell; Rachael V. Gallagher; Peter D. Wilson; Paul O. Downey; Lesley Hughes; Michelle R. Leishman (Global Change Biology, 2012)
We apply the concept of biodiversity hotspot analysis (the identification of biogeographical regions of high species diversity) to identify invasion hotspots – areas of potentially suitable climate for multiple non‐native plant species – in Australia under current and future climates. We used the species distribution model Maxent to model climate suitability surfaces for 72 taxa, recognized as ‘Weeds of National Significance’ (Wo NS ) in Australia, under current and projected climate for 2020 and 2050. Current climate suitability layers were summed across all 72 species, and we observed two regions of high climatic suitability corresponding to the top 25th percentile of combined climatic suitability values across Australia. We defined these as potential invasion hotspots. Areas of climatic suitability equivalent to the hotspot regions were identified in the composite maps for 2020 and 2050, to track spatial changes in the hotspots over the two time steps. Two potential invasion hotspot regions were identified under current and projected climates: the south west corner of Western Australia ( SW ), and south eastern Australia ( SE ). Herbarium data confirmed the presence of 73% and 99% of those species predicted to be in each hotspot respectively, suggesting that the SE has greater invasion potential. The area of both hotspots was predicted to retract southward and towards the coast under future climate scenarios, reducing in size by 81% ( SW ) and 71% ( SE ) by 2050. This reduction was driven by the dominance of southern temperate invasive plant species in the Wo NS list (47 of the 72), of which 44 were predicted to experience reductions in their bioclimatic range by 2050. While climate is likely to become less suitable for the majority of Wo NS in the future, potential invasion hotspots based on climate suitability are likely to remain in the far south of eastern Australia, and in the far south west of Western Australia by 2050.

Effects of climate change and wave direction on longshore sediment transport patterns in Southern California - Peter N. Adams; Douglas L. Inman; Jessica L. Lovering (Climatic Change, 2011)

Suppression of CFTR premature termination codons and rescue of CFTR protein and function by the synthetic aminoglycoside NB54 - Steven M. Rowe; Peter Sloane; Li Ping Tang; Kyle Backer; Marina Mazur; Jessica Buckley-Lanier; Igor Nudelman; Valery Belakhov; Zsuzsa Bebok; Erik Schwiebert; Timor Baasov; David M. Bedwell (Journal of Molecular Medicine, 2011)

Interactions of Thalassia testudinum and sediment biogeochemistry in Santa Rosa Sound, NW Florida - Richard Devereux; Diane F. Yates; Jessica Aukamp; Robert L. Quarles; Stephen J. Jordan; Roman S. Stanley; Peter M. Eldridge (Marine Biology Research, 2011)

Do Dispersing Monkeys Follow Kin? Evidence from Gray-cheeked Mangabeys (Lophocebus albigena) - Rebecca L. Chancellor; Jessica Satkoski; Debbie George; William Olupot; Nathanael Lichti; David G. Smith; Peter M. Waser (International Journal of Primatology, 2011)

Glacial clay affects foraging performance in a Patagonian fish and cladoceran - Mikael Jönsson; Lynn Ranåker; Alice Nicolle; Peter Ljungberg; Tony Fagerberg; Samuel Hylander; Therese Jephson; Karen Lebret; Jessica von Einem; Lars-Anders Hansson; P. Anders Nilsson; Esteban Balseiro; et al. (Hydrobiologia, 2011)

Dietary zinc mediates inflammation and protects against wasting and metabolic derangement caused by sustained cigarette smoke exposure in mice - Carol J. Lang; Michelle Hansen; Eugene Roscioli; Jessica Jones; Chiara Murgia; Margaret Leigh Ackland; Peter Zalewski; Gary Anderson; Richard Ruffin (BioMetals, 2011)

Dehalogenation of environmental pollutants in microbial electrolysis cells with biogenic palladium nanoparticles - Tom Hennebel; Jessica Benner; Peter Clauwaert; Lynn Vanhaecke; Peter Aelterman; Ruben Callebaut; Nico Boon; Willy Verstraete (Biotechnology Letters, 2011)

Historic fuel wood use in the Galápagos Islands: identification of charred remains - Cynthia A. Froyd; Jessica A. Lee; Atholl J. Anderson; Simon G. Haberle; Peter E. Gasson; Katherine J. Willis (Vegetation History and Archaeobotany, 2010)

The ‘Expansion-Contraction’ model of Pleistocene biogeography: rocky shores suffer a sea change? - PETER B. MARKO; JESSICA M. HOFFMAN; SANDRA A. EMME; TAMARA M. MCGOVERN; CARSON C. KEEVER; L. NICOLE COX (Molecular Ecology, 2010)

Anti-metastatic effects of liposomal gemcitabine in a human orthotopic LNCaP prostate cancer xenograft model - Peter Jantscheff; Vittorio Ziroli; Norbert Esser; Ralph Graeser; Jessica Kluth; Alena Sukolinskaya; Lenka A. Taylor; Clemens Unger; Ulrich Massing (Clinical & Experimental Metastasis, 2009)

Characterization of the wheat endosperm transfer cell-specific protein TaPR60 - Nataliya Kovalchuk; Jessica Smith; Margaret Pallotta; Rohan Singh; Ainur Ismagul; Serik Eliby; Natalia Bazanova; Andrew S. Milligan; Maria Hrmova; Peter Langridge; Sergiy Lopato (Plant Molecular Biology, 2009)

Coexistence of annual plants: Generalist seed predation weakens the storage effect - Jessica J. Kuang; Peter Chesson (Ecology, 2009)
We investigate the effect of seed predation on the coexistence of competing annual plants. We demonstrate a role for predation that is opposite to the conventional wisdom that predation promotes coexistence by reducing the intensity of competition. In the common situation where competitive coexistence involves intraspecific competition exceeding interspecific competition, predation can undermine coexistence by reducing the overall magnitude of competition, replacing competition with “apparent competition” in a way that does not lead to differential intraspecific and interspecific effects. We demonstrate this outcome in the case where coexistence occurs by “the storage effect” in a variable environment. The storage effect arises when the environment interacts with competition to create opportunities for species to increase from low density. Critical to the storage effect is positive covariance between the response of population growth to the environment and its response to competition, when a species is at high density. This outcome prevents species at high density from taking advantage of favorable environmental conditions. A species at low density has lower covariance and can take advantage of favorable environmental conditions, giving it an advantage over a high‐density species, fostering its recovery from low density. Hence, species coexistence is promoted. Here we find that density‐dependent predation lowers population densities, and so weakens competition, replacing competition with apparent competition, which does not covary with the environment. As a consequence, covariance between environment and competition is weakened, reducing the advantage to a species at low density. The species still strongly interact through the combination of competition and apparent competition, but the reduced low‐density advantage reduces their ability to coexist. Although this result is demonstrated specifically for the storage effect with a focus on annual plant communities, the principles involved are general ones.

Time for tea: mood, blood pressure and cognitive performance effects of caffeine and theanine administered alone and together - Peter J. Rogers; Jessica E. Smith; Susan V. Heatherley; C. W. Pleydell-Pearce (Psychopharmacology, 2007)

Ecology and ecosystem impacts of common buckthorn (Rhamnus cathartica): a review - Kathleen S. Knight; Jessica S. Kurylo; Anton G. Endress; J. Ryan Stewart; Peter B. Reich (Biological Invasions, 2007)

Evidence for a male-produced pheromone in Tetropium fuscum (F.) and Tetropium cinnamopterum (Kirby) (Coleoptera: Cerambycidae) - Peter J. Silk; Jon Sweeney; Junping Wu; Jessica Price; Jerzy M. Gutowski; Edward G. Kettela (The Science of Nature, 2007)

Cryptic speciation in the recently discovered American cycliophoran Symbion americanus; genetic structure and population expansion - Jessica M. Baker; Peter Funch; Gonzalo Giribet (Marine Biology, 2007)

Assessment of cognitive function in the heterozygous reeler mouse - Dilja D. Krueger; Jessica L. Howell; Britni F. Hebert; Peter Olausson; Jane R. Taylor; Angus C. Nairn (Psychopharmacology, 2006)

β2-Subunit-containing nicotinic acetylcholine receptors are involved in nicotine-induced increases in conditioned reinforcement but not progressive ratio responding for food in C57BL/6 mice - Darlene H. Brunzell; Jessica R. Chang; Brandon Schneider; Peter Olausson; Jane R. Taylor; Marina R. Picciotto (Psychopharmacology, 2006)

Weighting in LCA Based on Ecotaxes - Development of a Mid-point Method and Experiences from Case Studies - Peter Eldh; Jessica Johansson (The International Journal of Life Cycle Assessment, 2006)

PAQR Proteins: A Novel Membrane Receptor Family Defined by an Ancient7-Transmembrane Pass Motif - Y. Tom Tang; Tianhua Hu; Matthew Arterburn; Bryan Boyle; Jessica M. Bright; Peter C. Emtage; Walter D. Funk (Journal of Molecular Evolution, 2005)

Consistent production of cost-effective longSAGE libraries - Allison Clare Crawford; Jessica White; Peter Bundock; Giovanni Cordeiro; Shane McIntosh; Toni Pacey-Miller; Lee Rooke; Robert James Henry (Plant Molecular Biology Reporter, 2005)

A spatial model of tree α-diversity and tree density for the Amazon - Hans Ter Steege; Nigel Pitman; Daniel Sabatier; Hernan Castellanos; Peter Van Der Hout; Douglas C. Daly; Marcos Silveira; Oliver Phillips; Rodolfo Vasquez; Tinde Van Andel; Joost Duivenvoorden; Alexandre Adalardo De Oliveira; et al. (Biodiversity and Conservation, 2003)

Determination of the biological diatom index (IBD NF T 90–354): results of an intercomparison exercise - Jean Prygiel; Patrice Carpentier; Salomé Almeida; Michel Coste; Jean-Claude Druart; Luc Ector; Didier Guillard; Marie-Ange Honoré; Robert Iserentant; Peter Ledeganck; Christian Lalanne-Cassou; Christophe Lesniak; et al. (Journal of Applied Phycology, 2002)

Localization of organic anion transporting polypeptide 4 (Oatp4) in rat liver and comparison of its substrate specificity with Oatp1, Oatp2 and Oatp3 - Valentino Cattori; Jessica E. Montfoort; Bruno Stieger; Lukas Landmann; Dirk K. Meijer; Kaspar H. Winterhalter; Peter J. Meier; Bruno Hagenbuch (Pflügers Archiv - European Journal of Physiology, 2001)

Deconvolution of the three components of the photoacoustic signal by curve fitting and the relationship of CO2 uptake to proton fluxes - Hamed Tabrizi; Katrin Schinner; Jessica Spors; Ulf-Peter Hansen (Photosynthesis Research, 1998)